Light blue tempered glass
By plating the composite metal film layer on Sanyin low-radiation coated glass and performing off-site tempering treatment, the problem that Sanyin low-radiation coated glass in the prior art cannot be tempered in off-site, achieving the effect of high light-heat ratio and low energy consumption.
Patent Information
- Application Number
- CN202311200142.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-25
AI Technical Summary
The existing Sanyin low-radiation coating glass cannot achieve off-site tempering, and the light-heat ratio is not enough to meet the requirements of nearly zero energy-consuming buildings.
High-quality low-radiation coating tempered glass made of sputtering targets is made of specific nickel-chromium, silicon-aluminum, zinc-aluminum oxide, silver, zinc-tin oxide, zirconia, etc., and the composite metal film layer is coated on the glass substrate through vacuum magnetron sputtering technology, and the composite metal film layer is subjected to off-site tempering treatment in the tempering furnace.
The high light-heat ratio (≥1.7) is achieved, which meets the needs of nearly zero energy-consuming buildings, reduces building energy consumption, and can temper large-size glass in other places, improving production efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a low-radiation coated tempered glass and a preparation method thereof, and in particular to a low-radiation coated tempered glass for near-zero energy consumption buildings and a preparation method thereof, and belongs to the field of glass production and processing. Background Art
[0002] Reflective glass is also called reflective glass. Reflective glass is a glass surface coated with one or more layers of metal, alloy or metal compound film to change the optical properties of the glass to meet certain specific requirements. Reflective glass can be divided into the following categories according to the different characteristics of the product: heat reflective glass, low-emissivity glass (Low-E), conductive film glass, etc.
[0003] There are many methods for producing coated glass, such as vacuum magnetron sputtering, vacuum evaporation, chemical vapor deposition, and sol-gel. Magnetron sputtering coated glass can design and manufacture multi-layer complex film systems using magnetron sputtering technology, and can be coated with a variety of colors on a white glass substrate. The film layer has good corrosion resistance and wear resistance, and is currently the most produced and used technology. There is a certain gap between the variety and quality of vacuum evaporation coated glass and magnetron sputtering coated glass, and it has been gradually replaced by vacuum sputtering. Chemical vapor deposition is a technology that introduces reactive gas into the float glass production line to decompose on the hot glass surface and evenly deposit on the glass surface to form coated glass. This method requires less equipment investment, is easy to control, has low product cost, good chemical stability, and can be heat processed. It is one of the most promising production methods at present. The sol-gel method has a simple process for producing coated glass and good stability. The disadvantage is that the product light transmittance is too high and the decorative effect is poor.
[0004] Magnetron sputtering is the most widely used, most stable, best performance (emissivity E value ≤ 0.12), most abundant variety, and relatively low energy demand coated glass production process in the world. Since this production process does not need to be used together with the float glass production line, float glass production and glass coating process can be separated, which effectively reduces the repeated construction of float glass production lines by glass deep processing enterprises, reduces carbon dioxide emissions and related energy consumption. The most widely used heat-reflective glass and low-emissivity glass are basically produced by vacuum magnetron sputtering and chemical vapor deposition.
[0005] The principle of magnetron sputtering coating is to add an orthogonal magnetic field and electric field between the sputtered target (cathode) and the anode, fill the high vacuum chamber with the required inert gas (usually Ar gas), and the permanent magnet forms a magnetic field of 250-350 Gauss on the surface of the target material, which forms an orthogonal electromagnetic field with the high-voltage electric field. Under the action of the electric field, the argon gas is ionized into positive ions and electrons. A certain negative high voltage is applied to the target. The electrons emitted from the target are affected by the magnetic field and the ionization probability of the working gas increases, forming a high-density plasma near the cathode. The Ar ions are accelerated to fly to the target surface under the action of the Lorentz force, bombarding the target surface at a very high speed, and the atoms sputtered from the target fly to the glass substrate with a higher kinetic energy and deposit into a film.
[0006] At present, the most widely used heat-reflective glass and low-emissivity glass are basically produced by vacuum magnetron sputtering and chemical vapor deposition. Internationally famous vacuum magnetron sputtering equipment manufacturers include BOC (USA) and Leybold (Germany); chemical vapor deposition equipment manufacturers include Pilkington (UK), etc. At present, there are hundreds of coated glass manufacturers in my country. The vacuum magnetron sputtering manufacturers with greater influence in the industry include China Southern Glass Group Corporation and Shanghai Sunshine Coated Glass Company, etc., and chemical vapor deposition manufacturers include Shandong Bluestar Glass Company and Yangtze Float Glass Company, etc.
[0007] At present, low-emissivity coated glass has developed from single-silver Low-E glass to triple-silver Low-E glass. The triple-silver Low-E coated glass has achieved technical iterations of functions and off-site heat treatment processing, making a significant contribution to popularizing energy-saving glass / buildings and improving human living comfort. The light-to-heat ratio of existing coated glass cannot reach zero-energy buildings. The light-to-heat ratio of sunlight control coated glass is 0.5-0.9; the light-to-heat ratio of single-silver Low-E glass is 1.1-1.3; the light-to-heat ratio of double-silver Low-E glass is 1.4-1.7, which is poor in energy saving; although the light-to-heat ratio of existing triple-silver Low-E glass can reach 1.7-2.1, there is a technical problem that it cannot be tempered off-site.
[0008] The tempered low-emissivity glass of the present invention can adjust the light-to-heat ratio, which is high and reaches above 1.7 (visible light transmittance ÷ total solar energy transmittance ≈ light-to-heat ratio LSG); it solves the current problem of buildings requiring both high transmittance and low shading, appropriately lowers the heat transfer coefficient, and meets the national standard requirements for large curtain wall glass.
[0009] The low-E coated tempered glass of the present invention can be tempered and heat treated in a different place, the size of the treated glass is large, and the production efficiency is high, thus solving the technical problem that the existing triple-silver low-E coated glass cannot be tempered in a different place.
[0010] The present invention uses specific nickel-chromium, silicon-aluminum, zinc-aluminum oxide, silver, zinc-tin oxide, zirconium oxide and the like as sputtering target materials to produce high-quality low-radiation coated tempered glass, which has bright colors, is easy to adjust, has stable quality and high production efficiency; moreover, the low-radiation coated tempered glass produced by the method of the present invention has a higher reflectance ratio for medium and far infrared rays within the wavelength range of 4.5 to 25 microns, compared with the existing triple-silver Low-E glass; it greatly reduces building energy consumption, saves air conditioning and refrigeration costs in summer, and saves heating costs in winter; and the outdoor reflectivity of the product is low, the light is soft, which is far lower than the 16% required by national standards, and is particularly suitable for the "light pollution" demand for outdoor visible light reflection of high-rise and super-high-rise buildings in different regions, environments and scenes, and will not produce strong reflected light stimulation to the naked eye of people (especially drivers), thus avoiding alternating accidents and being suitable for long-term use.
[0011] Buildings using the triple-silver low-emissivity coated glass of the present invention meet the requirements of the national standard GB55015-2021 "General Specification for Building Energy Conservation and Renewable Energy Utilization" and comply with building energy conservation requirements.
[0012] Solar reflectivity, shading coefficient and total solar transmittance, solar reflectivity + absorptivity + transmittance = 100%. The lower the solar transmittance, the less outdoor heat enters the room, which saves more cooling costs in summer. The higher the indoor solar reflectivity, the more it can lock in the air conditioning in summer and the heating heat in winter and dissipate it to the outdoors through the glass.
[0013] The coated glass with different film layer structures has different colors and different glass properties. The film structure design of the low-emissivity coated tempered glass of the present invention is reasonable, the thickness design of the film layer is scientific, and the film structure setting position and thickness of the reflective layer (the second and third silver layers) are reasonable, which not only plays a reflective effect, but also can make the low-emissivity coated tempered glass of the present invention reflect relatively mild heat in the tempering furnace during the tempering process. The film layer remains intact under the condition of tempering stability without damaging the film layer, and the tempering treatment of large-scale coated glass can be carried out in a different location. Summary of the invention
[0014] The primary purpose of the present invention is to provide a light blue tempered glass to address the technical defect that buildings using existing triple-silver coated glass cannot meet the requirements of near-zero energy buildings. The light blue tempered glass of the present invention is a low-radiation coated glass with three layers of silver film, which is a coated glass for near-zero energy buildings. The light blue tempered glass of the present invention is a low-radiation coated glass, which can reduce the cooling and heating requirements of near-zero energy buildings, improve the energy efficiency of the energy system, and meet the requirements and standards of ultra-low energy consumption; buildings using the tempered coated glass of the present invention meet the requirements of the national standard GB55015-2021 "General Specification for Building Energy Conservation and Renewable Energy Utilization", and meet the requirements of building energy conservation.
[0015] To achieve the purpose of the present invention, the present invention provides a light blue tempered glass on one hand, comprising a composite metal film layer laminated on a tempered glass substrate, wherein the composite metal film layer comprises three metal silver film layers.
[0016] Among the three metal silver film layers, the first metal silver film layer is close to the tempered glass substrate, and between the first metal silver film layer and the tempered glass substrate are the silicon aluminum film layer, the zinc oxide aluminum film layer, and the nickel chromium film layer in sequence; the third metal silver film layer is far away from the tempered glass substrate, and between the third metal silver film layer and the glass surface are the nickel chromium film layer, the zinc oxide aluminum film layer, the silicon aluminum film layer and the zirconium oxide film layer on the glass surface in sequence; the second metal silver film layer is arranged between the first and third metal silver film layers.
[0017] Among them, a nickel-chromium film layer, a zinc-aluminum oxide film layer, a silicon-aluminum film layer, a zinc-aluminum oxide film layer, and a nickel-chromium film layer are stacked in sequence from the first metal silver film layer to the second metal silver film layer.
[0018] Wherein, a zinc tin oxide film layer is stacked between the second metal silver film layer and the third metal silver film layer, and the second and third metal silver film layers are symmetrically arranged on both sides of the zinc tin oxide film layer.
[0019] Particularly, the thickness of the zinc tin oxide film layer is 15.0-40.0 nm, preferably 25-35 nm.
[0020] A silicon aluminum film layer, a zinc aluminum oxide film layer, a nickel chromium film layer and a metal silver film layer are symmetrically stacked in sequence on both sides of the zinc tin oxide film layer.
[0021] In particular, from the second metal silver film layer to the third metal silver film layer, the 11th nickel-chromium film layer, the 12th zinc oxide aluminum film layer, the 13th silicon aluminum film layer, the 14th zinc tin oxide film layer, the 15th silicon aluminum film layer, the 16th zinc oxide aluminum film layer, and the 17th nickel-chromium film are stacked in sequence.
[0022] In particular, the thickness of the first metal silver film layer is 8.0-15.0 nm, preferably 10.0-13.0 nm; the thickness of the second metal silver film layer is 5.0-15.0 nm, preferably 8.0-10.0 nm; the thickness of the third metal silver film layer is 8.0-15.0 nm, preferably 10.0-13.0 nm.
[0023] In particular, the composite metal film layer includes a first silicon-aluminum alloy film layer, a second zinc-oxide aluminum alloy film layer, a third nickel-chromium alloy film layer, a fourth silver film layer, a fifth nickel-chromium alloy film layer, a sixth zinc-oxide aluminum alloy film layer, a seventh silicon-aluminum alloy film layer, an eighth zinc-oxide aluminum alloy film layer, a ninth nickel-chromium alloy film layer, a tenth silver film layer, an eleventh nickel-chromium alloy film layer, a twelfth zinc-oxide aluminum alloy film layer, a thirteenth silicon-aluminum alloy film layer, a fourteenth zinc-tin oxide alloy film layer, a fifteenth silicon-aluminum alloy film layer, a sixteenth zinc-oxide aluminum alloy film layer, a seventeenth nickel-chromium alloy film layer, an eighteenth silver film layer, a nineteenth nickel-chromium alloy film layer, a twentieth zinc-oxide aluminum alloy film layer, a twenty-first silicon-aluminum alloy film layer and a twenty-second zirconium oxide film layer stacked in sequence.
[0024] Another aspect of the present invention provides a light blue tempered glass, comprising composite metal film layers sequentially and tightly laminated on a tempered glass substrate, wherein the composite metal film layers sequentially comprise:
[0025] a first silicon-aluminum alloy film layer, located on the surface of the tempered glass substrate; a second zinc-oxide aluminum alloy film layer, located on the surface of the first silicon-aluminum alloy film layer; a third nickel-chromium alloy film layer, located on the surface of the second zinc-oxide aluminum alloy film layer; a fourth silver film layer, located on the surface of the third nickel-chromium alloy film layer; a fifth nickel-chromium alloy film layer, located on the surface of the fourth silver film layer; a sixth zinc-oxide aluminum alloy film layer, located on the surface of the fifth nickel-chromium alloy film layer; a seventh silicon-aluminum alloy film layer, located on the surface of the sixth zinc-oxide aluminum alloy film layer; an eighth zinc-oxide aluminum alloy film layer, located on the surface of the seventh silicon-aluminum alloy film layer; a ninth nickel-chromium alloy film layer, located on the surface of the eighth zinc-oxide aluminum alloy film layer; a tenth silver film layer, located on the surface of the ninth nickel-chromium alloy film layer; an eleventh nickel-chromium alloy film layer, located on the surface of the tenth silver film layer; a twelfth zinc-oxide aluminum alloy film layer, located on the surface of the eleventh a surface of a nickel-chromium alloy film layer; a thirteenth silicon-aluminum alloy film layer, located on the surface of the twelfth zinc-oxide-aluminum alloy film layer; a fourteenth zinc-tin oxide alloy film layer, located on the surface of the thirteenth silicon-aluminum alloy film layer; a fifteenth silicon-aluminum alloy film layer, located on the surface of the fourteenth zinc-tin oxide alloy film layer; a sixteenth zinc-oxide-aluminum alloy film layer, located on the surface of the fifteenth silicon-aluminum alloy film layer; a seventeenth nickel-chromium alloy film layer, located on the surface of the sixteenth zinc-oxide-aluminum alloy film layer; an eighteenth silver film layer, located on the surface of the seventeenth nickel-chromium alloy film layer; a nineteenth nickel-chromium alloy film layer, located on the surface of the eighteenth silver film layer; a twentieth zinc-oxide-aluminum alloy film layer, located on the surface of the nineteenth nickel-chromium alloy film layer; a twenty-first silicon-aluminum alloy film layer, located on the surface of the twentieth zinc-oxide-aluminum alloy film layer; a twenty-second zirconium oxide alloy film layer, located on the surface of the twenty-first silicon-aluminum alloy film layer.
[0026] Among them, the thickness of the first silicon aluminum alloy film layer is 55.0-65.0nm, preferably 55.3-61.7nm; the thickness of the second zinc oxide aluminum alloy film layer is 10.0-30.0nm, preferably 15.0-25.0nm; the thickness of the third nickel chromium alloy layer is 0.5-3.0nm, preferably 1.0-2.0nm; the thickness of the fourth silver film layer is 8.0-15.0nm, preferably 10.0-13.0nm; the thickness of the fifth nickel chromium alloy film layer is 0.5-3.0nm, preferably 1.0-2.0nm; the thickness of the sixth zinc oxide aluminum alloy film layer is 15.0-25.0nm, preferably 1.0-2.0nm. The thickness of the seventh silicon aluminum alloy film layer is 300.0-420.0nm, preferably 320.0-350.0nm; the thickness of the eighth zinc oxide aluminum alloy film layer is 15.0-25.0nm, preferably 15-22.0nm; the thickness of the ninth nickel-chromium alloy film layer is 1.0-5.0nm, preferably 2.0-4.0nm; the thickness of the tenth silver film layer is 5.0-15.0nm, preferably 8.0-10.0nm; the thickness of the eleventh nickel-chromium alloy film layer is 1.5-3.5nm, preferably 1.5-2.5nm; the thickness of the twelfth zinc oxide aluminum alloy film layer is 1 The thickness of the thirteenth silicon aluminum alloy film layer is 130.0-200.0nm, preferably 140.0-170.0nm; the thickness of the fourteenth zinc oxide tin alloy film layer is 15.0-40.0nm, preferably 20.0-35.0nm; the thickness of the fifteenth silicon aluminum alloy film layer is 110.0-150.0nm, preferably 114-128.0nm; the thickness of the sixteenth zinc oxide aluminum alloy film layer is 15.0-30.0nm, preferably 17.0-25.0nm; the thickness of the seventeenth nickel chromium alloy film layer is 1.0-3.0 nm, preferably 1.5-2.5nm; the thickness of the eighteenth silver film layer is 8.0-15.0nm, preferably 10.0-13.0nm; the thickness of the nineteenth nickel-chromium alloy film layer is 1.0-3.0nm, preferably 1.5-2.5nm; the thickness of the twentieth zinc oxide aluminum alloy film layer is 10.0-30.0nm, preferably 15.0-25.0nm; the thickness of the twenty-first silicon aluminum alloy film layer is 150.0-180.0nm, preferably 155.0-170.0nm; the thickness of the twenty-second zirconium oxide alloy film layer is 10.0-50.0nm, preferably 20.0-35.0nm.
[0027] In particular, on one surface of the tempered glass substrate, the first silicon-aluminum alloy film is stacked in sequence from bottom to top; the second zinc-oxide aluminum alloy film is stacked; the third nickel-chromium alloy film is stacked; the fourth silver film is stacked; the fifth nickel-chromium alloy film is stacked; the sixth zinc-oxide aluminum alloy film is stacked; the seventh silicon-aluminum alloy film is stacked; the eighth zinc-oxide aluminum alloy film is stacked; the ninth nickel-chromium alloy film is stacked; the tenth silver film is stacked; the eleventh nickel-chromium alloy film is stacked; the twelfth zinc-oxide aluminum alloy film is stacked; the thirteenth silicon-aluminum alloy film is stacked; the fourteenth zinc-tin oxide alloy film is stacked; the fifteenth silicon-aluminum alloy film is stacked; the sixteenth zinc-oxide aluminum alloy film is stacked; the seventeenth nickel-chromium alloy film is stacked; the eighteenth silver film is stacked; the nineteenth nickel-chromium alloy film is stacked; the twentieth zinc-oxide aluminum alloy film is stacked; the twenty-first silicon-aluminum alloy film is stacked; and the twenty-second zirconium oxide film is stacked.
[0028] In particular, the transmittance color value of the single low-emissivity coated tempered glass is 80≤L * ≤90, -10≤a * ≤-5, -3≤b * ≤3; reflective color value is 28≤L * ≤35,0≤a * ≤5, -15≤b * ≤-8.
[0029] In particular, the transmittance color value of the single low-emissivity coated tempered glass is 86≤L * ≤88, -7≤a * ≤-5, 0≤b * ≤1; reflective color value is 30≤L * ≤32, 2≤a * ≤4, -11≤b * ≤-9.
[0030] Another aspect of the present invention provides a light blue tempered glass prepared by performing the steps in the following order:
[0031] 1) Sintering target
[0032] The target materials silicon aluminum alloy, zinc oxide aluminum alloy, silver, nickel chromium alloy, zinc oxide tin, and zirconium oxide are sintered on the target position of the vacuum sputtering chamber of the glass coating machine respectively for standby use;
[0033] 2) Glass pretreatment
[0034] The glass substrate to be coated is placed in a vacuum state to perform dehumidification and degassing treatment to reduce the moisture and gas deposited on the glass surface to obtain a dehumidified and degassed glass substrate;
[0035] 3) Coating treatment
[0036] The dehumidified and degassed glass substrate is sent into the vacuum magnetron sputtering target chamber of the glass coating machine which is sintered with silicon aluminum alloy, zinc oxide aluminum alloy, nickel chromium alloy, silver, zinc oxide tin alloy and zirconium oxide target materials respectively, and the surface of the dehumidified and degassed glass substrate is subjected to plating treatment in sequence of the first silicon aluminum film layer; the second zinc oxide aluminum film layer; the third nickel chromium alloy film layer; the fourth silver film layer; the fifth nickel chromium alloy film layer; the sixth zinc oxide aluminum film layer; the seventh silicon aluminum film layer; the eighth zinc oxide aluminum film layer; the ninth nickel chromium alloy film layer; the tenth silver film layer; the eleventh nickel chromium gold film layer; the twelfth zinc oxide aluminum film layer; the thirteenth silicon aluminum film layer; the fourteenth zinc tin oxide film layer; the fifteenth silicon aluminum film layer; the sixteenth zinc oxide aluminum film layer; the seventeenth nickel chromium alloy film layer; the eighteenth silver film layer; the nineteenth nickel chromium alloy film layer; the twentieth zinc oxide aluminum film layer; the twenty-first silicon aluminum film layer; and the twenty-second zirconium oxide film layer;
[0037] 4) Tempered treatment
[0038] The coated glass is sent into a tempering furnace for tempering to produce low-emissivity coated tempered glass.
[0039] The silicon aluminum alloy selected in step 1) has a sintering purity of ≥99.90% and a density of ≥2.19 g / cm 3 , a silicon-aluminum alloy with a relative density of ≥93% and a melting point of 1370°C, wherein the Al content is 8-12±2wt%, and the rest is Si; the zinc oxide aluminum alloy selectively sintered with a purity of ≥99.90%, a theoretical density of 5.56 ((ZnO)-2wt% (Al2O3)), a target density of ≥5.50g / cm3, a relative density of ≥99%, and composed of 2wt% Al2O3 and 98wt% ZnO; the silver selectively sintered with a purity of ≥99.99% and a theoretical density of ≥10.49g / cm 3 , target density is ≥10.28g / cm 3 , silver metal with a relative density of ≥98% and a melting point of 960°C; the nickel-chromium alloy selected for sintering has a purity of ≥99.7%, a theoretical density of 8.49 (Ni-20%Cr), and a target density of ≥8.5g / cm 3 , a nickel-chromium alloy with a relative density of ≥98% and a melting point of 1420°C, wherein the Cr content is 20±1wt% and the rest is Ni; the zinc oxide tin alloy is selected to have a sintering purity of ≥99.9%, a Sn content of (50±2)wt% and the rest is Sn, and a density of ≥7.1g / cm 3 , a zinc oxide tin alloy with a melting point of 360°C; the purity of the zirconium oxide target is ≥99.9% and the density is ≥5.35g / cm 3 , melting point is 2300℃.
[0040] In particular, the sintering time of the silicon-aluminum alloy is 90 minutes; the sintering time of the nickel-chromium alloy is 90 minutes; the sintering time of the silver is 60 minutes; the sintering time of the zinc oxide-aluminum alloy is 60 minutes; the sintering time of the zinc oxide-tin alloy is 90 minutes; and the sintering time of the pick oxide is 90 minutes.
[0041] In particular, the target materials silicon aluminum alloy, zinc oxide aluminum alloy, silver, nickel chromium alloy, zinc oxide tin alloy and zirconium oxide meet the requirements of silicon aluminum target, zinc oxide aluminum alloy, silver, nickel chromium alloy, zinc oxide tin alloy and zirconium oxide in the national industry standard JC / T2068-2011 respectively.
[0042] The zinc oxide tin alloy film of the present invention is used to absorb the reflection brightness of the third layer of silver (ie, the eighteenth silver film layer) and adjust the color of the coated glass.
[0043] The dehumidification and degassing treatment in step 2) is to divide the glass to be coated into two treatment stages to reduce the moisture and gas deposited on the surface of the glass, so as to obtain the dehumidified and degassed glass.
[0044] In particular, the absolute pressure in the first process stage of the dehumidification and degassing process is higher than the absolute pressure in the second process stage.
[0045] In particular, the absolute pressure during the first treatment stage is 5.0 to 6.0 × 10 -2 mbar; the absolute pressure during the second treatment stage is 3.0~6.0×10 -5 mbar.
[0046] In particular, the processing temperature of the first processing stage is -135 to -145°C, and the glass processing speed is 2.0-10m / min, preferably 3.0-8.0m / min, and more preferably 5m / min; the processing temperature of the second processing stage is 80-100°C, and the glass processing speed is 2.0 to 10.0m / min, preferably 3.0 to 8.0m / min, and more preferably 5m / min.
[0047] In particular, the treatment time of the first dehumidification and degassing treatment stage is 15 to 60 seconds, preferably 20 to 40 seconds, and more preferably 20 to 30 seconds; the treatment time of the second dehumidification and degassing treatment stage is 15 to 60 seconds, preferably 20 to 40 seconds, and more preferably 20 to 30 seconds.
[0048] In particular, in step 2), the glass substrate is first cleaned with deionized water and then placed in a vacuum state to perform the dehumidification and degassing treatment to reduce the water and gas deposited on the glass surface, thereby obtaining a dehumidified and degassed glass substrate;
[0049] Wherein, the content of minerals in the deionized water is ≤5μ / cm / m 2 ; The temperature is 35 to 40°C; The cleaning speed is 2.0 to 10.0 m / min, preferably 3.0 to 8.0 m / min, and more preferably 5 m / min.
[0050] In particular, the method further comprises drying the glass substrate after being cleaned with deionized water at 20-50° C. to remove water droplets on the glass surface, wherein the drying speed is 5 m / min.
[0051] Wherein, in step 3), the thickness of the first silicon-aluminum alloy film layer is 55.0-65.0 nm; the thickness of the second zinc-aluminum alloy film layer is 10.0-30.0 nm; the thickness of the third nickel-chromium alloy layer is 0.5-3.0 nm; the thickness of the fourth silver film layer is 8.0-15.0 nm; the thickness of the fifth nickel-chromium alloy film layer is 0.5-3.0 nm; the thickness of the sixth zinc-aluminum alloy film layer is 15.0-25.0 nm; the thickness of the seventh silicon-aluminum alloy film layer is 300.0-420.0 nm; the thickness of the eighth zinc-aluminum alloy film layer is 15.0-25.0 nm; the thickness of the ninth nickel-chromium alloy film layer is 1.0-5.0 nm; the thickness of the tenth silver film layer is 5.0-15.0 nm; the thickness of the eleventh nickel-chromium alloy film layer is 1.5-3.5 nm; the thickness of the twelfth zinc-aluminum alloy film layer is 1. The thickness of the gold film layer is 15.0-50.0nm; the thickness of the thirteenth silicon-aluminum alloy film layer is 130.0-200.0nm; the thickness of the fourteenth zinc-tin oxide alloy film layer is 15.0-40.0nm; the thickness of the fifteenth silicon-aluminum alloy film layer is 110.0-150.0nm; the thickness of the sixteenth zinc-aluminum oxide alloy film layer is 15.0-30.0nm; the thickness of the seventeenth nickel-chromium alloy film layer is 1.0-3.0nm; the thickness of the eighteenth silver film layer is 8.0-15.0nm; the thickness of the nineteenth nickel-chromium alloy film layer is 1.0-3.0nm; the thickness of the twentieth zinc-aluminum oxide alloy film layer is 10.0-30.0nm; the thickness of the twenty-first silicon-aluminum alloy film layer is 150.0-180.0nm; the thickness of the twenty-second zirconium oxide alloy film layer is 10.0-50.0nm.
[0052] In particular, the thickness of the first silicon aluminum alloy film layer is 55.3-61.7nm; the thickness of the second zinc oxide aluminum alloy film layer is 15.0-25.0nm; the thickness of the third nickel chromium alloy layer is 1.0-2.0nm; the thickness of the fourth silver film layer is 10.0-13.0nm; the thickness of the fifth nickel chromium alloy film layer is 1.0-2.0nm; the thickness of the sixth zinc oxide aluminum alloy film layer is 18.0-23nm; the thickness of the seventh silicon aluminum alloy film layer is 320.0-350.0nm; the thickness of the eighth zinc oxide aluminum alloy film layer is 15-22.0nm; the thickness of the ninth nickel chromium alloy film layer is 2.0-4.0nm; the thickness of the tenth silver film layer is 8.0-10.0nm; the thickness of the eleventh nickel chromium alloy film layer is 1.5-2.5nm; the twelfth zinc oxide aluminum alloy film layer The thickness of the thirteenth silicon aluminum alloy film layer is 140.0-170.0nm; the thickness of the fourteenth zinc oxide tin alloy film layer is 20.0-35.0nm; the thickness of the fifteenth silicon aluminum alloy film layer is 114-128.0nm; the thickness of the sixteenth zinc oxide aluminum alloy film layer is 17.0-25.0nm; the thickness of the seventeenth nickel chromium alloy film layer is 1.5-2.5nm; the thickness of the eighteenth silver film layer is 10.0-13.0nm; the thickness of the nineteenth nickel chromium alloy film layer is 1.5-2.5nm; the thickness of the twentieth zinc oxide aluminum alloy film layer is 15.0-25.0nm; the thickness of the twenty-first silicon aluminum alloy film layer is 155.0-170.0nm; the thickness of the twenty-second zirconium oxide alloy film layer is 20.0-35.0nm.
[0053] In particular, the vacuum state during the coating process in step 3) is: the absolute pressure in the vacuum magnetron sputtering chamber is maintained at 2.0 to 4.0×10 -5 mbar, preferably 3.0×10 -5 mbar; the plating speed is 2 to 10 m / min, preferably 3 to 8.0 m / min, and more preferably 5 m / min; the plating temperature is 80 to 100°C.
[0054] In particular, the first silicon-aluminum alloy film layer is formed by two plating treatments; the seventh silicon-aluminum alloy film layer is formed by six plating treatments; the thirteenth silicon-aluminum alloy film layer is formed by four plating treatments; the fifteenth silicon-aluminum alloy film layer is formed by two plating treatments; the twenty-first silicon-aluminum alloy film layer is formed by four plating treatments; the eighth zinc oxide aluminum alloy film layer is formed by two plating treatments; the twelfth zinc oxide aluminum alloy film layer is formed by two plating treatments; the fourteenth zinc oxide tin alloy film layer is formed by two plating treatments; and the twenty-second zirconium oxide film layer is formed by two plating treatments.
[0055] In particular, the first silicon-aluminum alloy film layer is plated twice; wherein: during the first plating process, the vacuum magnetron sputtering voltage is 380.0~480.0V, preferably 410.0~450.0V; the current is 45.0~100.0A, preferably 60.0~80.0A; the power is 20.0~50.0Kw, preferably 25.0~35.0kW; during the second plating process, the vacuum magnetron sputtering voltage is 380.0~480.0V, preferably 410.0~440.0V; the current is 45.0~100.0A, preferably 65.0~90.0A; the power is 20.0~50.0Kw, preferably 25.0~35.0kw.
[0056] Particularly, the atmosphere in the vacuum magnetron sputtering chamber during the first and second plating processes of the first silicon-aluminum alloy film layer is argon and nitrogen.
[0057] In particular, the volume ratio of argon to nitrogen in the atmosphere in the sputtering chamber during the first plating process is 2:3; and the volume ratio of argon to nitrogen in the atmosphere in the sputtering chamber during the second plating process is 2:3.
[0058] In particular, during the first plating process, the flow rate of argon gas is 400±5sc / cm, preferably 400sc / cm; the flow rate of nitrogen gas is 600±5sc / cm, preferably 600sc / cm; during the second plating process, the flow rate of argon gas is 400±5sc / cm, preferably 400sc / cm; the flow rate of nitrogen gas is 600±5sc / cm, preferably 600sc / cm.
[0059] In particular, in the coating process of the second zinc oxide aluminum alloy film layer in step 3), the magnetron sputtering voltage is 350.0-470.0V, preferably 410.0-450.0V; the current is 30.0-60.0A, preferably 40.0-55.0A; the power is 10.0-40.0Kw, preferably 15.0-30.0Kw.
[0060] Particularly, the atmosphere in the vacuum sputtering chamber during the coating process of the second zinc oxide aluminum alloy film layer is argon and oxygen.
[0061] In particular, the volume ratio of argon to oxygen in the atmosphere is 16:1.
[0062] In particular, the argon flow rate is 800±5 sc / cm, preferably 800 sc / cm, and the oxygen flow rate is 50±5 sc / cm, preferably 50 sc / cm.
[0063] In particular, during the plating process of the third nickel-chromium alloy film layer in step 3), the magnetron sputtering voltage is 260.0-310.0V, preferably 270.0-300.0V; the current is 3.0-10.0A, preferably 4.5-6.0A; the power is 0.5-3.0Kw, preferably 1.0-2.0Kw.
[0064] In particular, the atmosphere in the vacuum sputtering chamber during the deposition of the third nickel-chromium alloy layer is argon.
[0065] In particular, the argon gas flow rate is 700±5 sc / cm, preferably 700 sc / cm.
[0066] In particular, during the plating process of the fourth silver film layer in step 3), the magnetron sputtering voltage is 350.0-420.0 V, preferably 360.0-390.0 V; the current is 20.0-50.0 A, preferably 25.0-40.0 A; and the power is 5.0-20.0 Kw, preferably 8.0-15.0 Kw.
[0067] Particularly, the atmosphere in the vacuum sputtering chamber during the coating process of the fourth silver film layer is argon.
[0068] Particularly, the flow rate of the argon gas is 600±5 sc / cm, preferably 600 sc / cm.
[0069] In particular, during the plating process of the fifth nickel-chromium alloy film layer in step 3), the magnetron sputtering voltage is 350.0-420.0V, preferably 370.0-400.0V; the current is 3.0-10.0A, preferably 4.0-6.0A; the power is 0.5-5.0Kw, preferably 1.0-2.5Kw.
[0070] Particularly, during the plating process of the fifth nickel-chromium alloy film layer, the atmosphere in the vacuum magnetron sputtering chamber is argon.
[0071] Particularly, the flow rate of the argon gas is 700±5 sc / cm, preferably 700 sc / cm.
[0072] The flow rate of the gas component in the coating process of the present invention is the corresponding flow rate ±5sc / cm.
[0073] In particular, during the plating process of the sixth zinc oxide aluminum alloy film layer in step 3), the magnetron sputtering voltage is 380.0-460.0V, preferably 410.0-440.0V; the current is 25.0-60.0A, preferably 35.0-50.0A; and the power is 12.0-35.0Kw, preferably 15.0-25.0Kw.
[0074] Particularly, the atmosphere in the vacuum sputtering chamber during the coating process of the sixth zinc oxide aluminum alloy film layer is argon and oxygen.
[0075] In particular, the volume ratio of argon to oxygen in the atmosphere is 16:1.
[0076] In particular, the flow rate of argon gas is 800 sc / cm, and the flow rate of oxygen gas is 50 sc / cm.
[0077] In particular, the seventh silicon-aluminum alloy film layer in step 3) is plated six times, wherein:
[0078] During the first plating process, the vacuum magnetron sputtering voltage is 580.0 to 680.0 V, preferably 610.0 to 650.0 V; the current is 100.0 to 150.0 A, preferably 110.0 to 130.0 A; the power is 50.0 to 80.0 Kw, preferably 60.0 to 70.0 kW;
[0079] During the second plating process, the vacuum magnetron sputtering voltage is 560.0-630.0V, preferably 580.0-610.0V; the current is 100.0-150.0A, preferably 110.0-135.0A; the power is 50.0-80.0Kw, preferably 60-75.0kW;
[0080] During the third plating process, the vacuum magnetron sputtering voltage is 460.0-520.0V, preferably 480.0-510.0V; the current is 130.0-180.0A, preferably 140.0-170.0A; the power is 50.0-85.0Kw, preferably 60.0-72.0kW;
[0081] During the fourth plating process, the vacuum magnetron sputtering voltage is 380.0-450.0V, preferably 400.0-430.0V; the current is 40.0-80.0A, preferably 55.0-70.0A; the power is 15.0-50.0Kw, preferably 20.0-35.0kW;
[0082] During the fifth plating process, the vacuum magnetron sputtering voltage is 480.0-530.0V, preferably 490.0-515.0V; the current is 120.0-160.0A, preferably 130.0-150.0A; the power is 40.0-80.0Kw, preferably 50.0-70.0kW;
[0083] During the sixth plating process, the vacuum magnetron sputtering voltage is 400.0-490.0V, preferably 440.0-460.0V; the current is 110.0-160.0A, preferably 120.0-140.0A; and the power is 30.0-80.0Kw, preferably 40.0-60.0kW.
[0084] In the present invention, the seventh silicon-aluminum film layer has a relatively large thickness, and multiple plating processes are used to improve the plating efficiency and, more importantly, to improve the uniformity of the film layer.
[0085] The function of the first silicon-aluminum film layer of the present invention is to improve the adhesion between other film layers and the original glass sheet; the 21st silicon-aluminum film layer is a protective layer, and its function is to protect the internal processing of the processing plant to prevent the coated glass from being scratched and damaged during subsequent processing; the functions of the middle 7th, 13th and 15th silicon-aluminum film layers are: to achieve adhesion with the 8th and 16th zinc oxide aluminum alloy film layers and the 14th zinc oxide tin alloy film layer (other materials are not firmly bonded to the zinc oxide aluminum alloy) and to adjust the color of the coated glass.
[0086] Particularly, during the coating process of the seventh silicon-aluminum alloy film layer, the atmosphere in the magnetron sputtering chamber is argon and nitrogen.
[0087] In particular, the volume ratio of argon to nitrogen in the atmosphere during the first and second plating processes of the seventh silicon-aluminum alloy film layer is 2.1:3.
[0088] In particular, the flow rate of the argon gas is 420 sc / cm; the flow rate of the nitrogen gas is 600 sc / cm.
[0089] In particular, the volume ratio of argon to nitrogen in the atmosphere during the third and sixth plating processes of the seventh silicon aluminum alloy film layer is 5:7.
[0090] Particularly, the flow rate of the argon gas is 500 sc / cm; the flow rate of the nitrogen gas is 700 sc / cm.
[0091] In particular, the volume ratio of argon to nitrogen in the atmosphere during the fourth and fifth plating processes of the seventh silicon aluminum alloy film layer is 5:6.
[0092] Particularly, the flow rate of the argon gas is 500 sc / cm; the flow rate of the nitrogen gas is 600 sc / cm.
[0093] In particular, the eighth zinc oxide aluminum alloy film layer in step 3) is plated twice.
[0094] Among them, during the first plating process, the vacuum magnetron sputtering voltage is 430.0~480.0V, preferably 450.0~465.0V; the current is 25.0~60.0A, preferably 30.0~40.0A; the power is 8.0~30.0Kw, preferably 8.5~12.0Kw; during the second plating process, the vacuum magnetron sputtering voltage is 430.0~480.0V, preferably 450.0~465.0V; the current is 25.0~60.0A, preferably 30.0~40.0A; the power is 8.0~30.0Kw, preferably 8.5~12.0Kw.
[0095] Particularly, the atmosphere in the magnetron sputtering chamber during the first and second plating processes of the eighth zinc oxide aluminum alloy film layer is argon and oxygen.
[0096] In particular, the volume ratio of argon to oxygen in the atmosphere is 16:1.
[0097] In particular, the flow rate of argon gas is 800 sc / cm, and the flow rate of oxygen gas is 50 sc / cm.
[0098] In particular, during the plating process of the ninth nickel-chromium alloy film layer in step 3), the magnetron sputtering voltage is 280.0-330.0 V, preferably 290.0-310.0 V; the current is 6.0-20.0 A, preferably 8.0-12.0 A; the power is 1.5-5.0 Kw, preferably 2.0-3.5 Kw.
[0099] Particularly, the atmosphere in the magnetron sputtering chamber during the plating process of the ninth nickel-chromium alloy film layer is argon.
[0100] Particularly, the flow rate of the argon gas is 700 sc / cm.
[0101] In particular, during the plating process of the tenth silver film layer in step 3), the magnetron sputtering voltage is 410.0-450.0 V, preferably 415.0-440.0 V; the current is 15.0-40.0 A, preferably 20.0-30.0 A; and the power is 5.0-20.0 Kw, preferably 8.0-12.0 Kw.
[0102] Particularly, the atmosphere in the sputtering chamber during the coating process of the tenth silver film layer is argon.
[0103] Particularly, the flow rate of the argon gas is 500 sc / cm.
[0104] In particular, during the plating process of the eleventh nickel-chromium alloy layer in step 3), the magnetron sputtering voltage is 380.0-450.0 V, preferably 400.0-420.0 V; the current is 5.0-10.0 A, preferably 6.0-8.0 A; and the power is 1.0-8.0 Kw, preferably 1.2-2.5 Kw.
[0105] Particularly, the atmosphere in the sputtering chamber during the plating process of the eleventh nickel-chromium alloy layer is argon.
[0106] Particularly, the argon gas flow rate is 600 sc / cm.
[0107] In particular, the twelfth zinc oxide aluminum alloy film layer in step 3) is plated twice.
[0108] Among them, during the first plating process, the vacuum magnetron sputtering voltage is 430.0~500.0V, preferably 450.0~480.0V; the current is 28.0~50.0A, preferably 30.0~40.0A; the power is 10.0~30.0Kw, preferably 13.0~20.0Kw; during the second plating process, the vacuum magnetron sputtering voltage is 430.0~500.0V, preferably 460.0~480.0V; the current is 28.0~50.0A, preferably 30.0~40.0A; the power is 10.0~30.0Kw, preferably 13.0~20.0Kw.
[0109] Particularly, the atmosphere in the sputtering chamber during the first and second plating processes of the twelfth zinc oxide aluminum alloy film layer is argon and oxygen.
[0110] In particular, the volume ratio of argon to oxygen in the atmosphere is 16:1.
[0111] In particular, the flow rate of argon gas is 800 sc / cm, and the flow rate of oxygen gas is 50 sc / cm.
[0112] In particular, the thirteenth silicon-aluminum alloy film layer in step 3) is plated four times.
[0113] Wherein, during the first plating process, the vacuum magnetron sputtering voltage is 440.0-490.0V, preferably 450.0-470.0V; the current is 110.0-160.0A, preferably 125.0-150.0A; the power is 35.0-80.0Kw, preferably 45.0-65.0kW;
[0114] During the second plating process, the vacuum magnetron sputtering voltage is 380.0-430.0V, preferably 390.0-410.0V; the current is 45.0-90.0A, preferably 60.0-80.0A; the power is 15.0-40.0Kw, preferably 20.0-32.0kW;
[0115] During the third plating process, the vacuum magnetron sputtering voltage is 430.0-500.0V, preferably 450.0-490.0V; the current is 110.0-150.0A, preferably 120.0-140.0A; the power is 40.0-70.0Kw, preferably 45.0-65.0kW;
[0116] During the fourth plating process, the vacuum magnetron sputtering voltage is 380.0-450.0V, preferably 390.0-425.0V; the current is 50.0-80.0A, preferably 60.0-72.0A; and the power is 15.0-40.0Kw, preferably 20.0-35.0kW.
[0117] Particularly, the atmospheres during the first, second, third and fourth plating processes of the thirteenth silicon-aluminum alloy film layer are argon and nitrogen.
[0118] In particular, during the first plating process of the thirteenth silicon aluminum alloy film layer, the volume ratio of argon to nitrogen in the atmosphere is 2.4:3.
[0119] In particular, the flow rate of the argon gas is 480 sc / cm; the flow rate of the nitrogen gas is 600 sc / cm.
[0120] In particular, the volume ratio of argon gas to nitrogen gas during the second and fourth plating processes of the thirteenth silicon aluminum alloy film layer is 1:1.1.
[0121] In particular, the flow rate of the argon gas is 500 sc / cm; the flow rate of the nitrogen gas is 550 sc / cm.
[0122] In particular, during the third plating process of the thirteenth silicon aluminum alloy film layer, the volume ratio of argon to nitrogen in the atmosphere is 4.7:6.
[0123] In particular, the flow rate of the argon gas is 470 sc / cm; the flow rate of the nitrogen gas is 600 sc / cm.
[0124] In particular, the zinc-tin oxide alloy film layer in step 3) is plated twice.
[0125] Among them, during the first plating process, the vacuum magnetron sputtering voltage is 300.0~380.0V, preferably 310.0~360.0V; the current is 30.0~70.0A, preferably 35.0~55.0A; the power is 10.0~30.0Kw, preferably 13.0~20.0Kw; during the second plating process, the vacuum magnetron sputtering voltage is 300.0~380.0V, preferably 310.0~360.0V; the current is 30.0~70.0A, preferably 35.0~55.0A; the power is 10.0~30.0Kw, preferably 13.0~20.0Kw.
[0126] Particularly, the atmosphere in the sputtering chamber during the first and second plating processes of the fourteenth zinc oxide tin alloy film layer is argon.
[0127] Particularly, the argon gas flow rate is 800 sc / cm.
[0128] In particular, the fifteenth silicon-aluminum alloy film layer in step 3) is plated twice, wherein:
[0129] During the first plating process, the vacuum magnetron sputtering voltage is 450.0-510.0V, preferably 460.0-490.0V; the current is 110.0-180.0A, preferably 135.0-160.0A; the power is 35.0-80.0Kw, preferably 50.0-70.0kW;
[0130] During the second plating process, the vacuum magnetron sputtering voltage is 450.0-550.0V, preferably 485.0-520.0V; the current is 120.0-170.0A, preferably 130.0-160.0A; the power is 45.0-80.0Kw, preferably 52.0-70.0kW;.
[0131] Particularly, the atmosphere in the magnetron sputtering chamber during the first and second plating processes of the fifteenth silicon-aluminum alloy film layer is argon and nitrogen.
[0132] In particular, the volume ratio of argon to nitrogen in the atmosphere is 5:5.8.
[0133] In particular, the flow rate of the argon gas is 500 sc / cm; the flow rate of the nitrogen gas is 580 sc / cm.
[0134] In particular, during the plating process of the sixteenth zinc oxide aluminum alloy film layer in step 3), the magnetron sputtering voltage is 480.0-560.0V, preferably 510.0-550.0V; the current is 30.0-70.0A, preferably 45.0-60.0A; the power is 18.0-35.0Kw, preferably 18.5-30.0Kw.
[0135] Particularly, during the plating process of the sixteenth zinc oxide aluminum alloy film layer, the atmosphere in the sputtering chamber is argon and oxygen.
[0136] In particular, the volume ratio of argon to oxygen in the atmosphere is 16:1.
[0137] In particular, the flow rate of argon gas is 800 sc / cm, and the flow rate of oxygen gas is 50 sc / cm.
[0138] In particular, during the plating process of the seventeenth nickel-chromium alloy layer in step 3), the magnetron sputtering voltage is 320.0-400.0V, preferably 340.0-380.0V; the current is 2.0-10.0A, preferably 4.0-8.0A; and the power is 0.5-6.0Kw, preferably 1-4Kw.
[0139] Particularly, the atmosphere in the vacuum sputtering chamber during the plating process of the seventeenth nickel-chromium alloy layer is argon.
[0140] Particularly, the argon gas flow rate is 750 sc / cm.
[0141] In particular, during the plating process of the eighteenth silver film layer in step 3), the magnetron sputtering voltage is 380.0-450.0V, preferably 400.0-430.0V; the current is 15.0-40.0A, preferably 20.0-30.0A; the power is 5.0-20.0Kw, preferably 8.0-15.0Kw.
[0142] Particularly, the atmosphere in the vacuum sputtering chamber during the plating process of the eighteenth silver film layer is argon.
[0143] Particularly, the flow rate of the argon gas is 600 sc / cm.
[0144] In particular, during the plating process of the nineteenth nickel-chromium alloy layer in step 3), the magnetron sputtering voltage is 380.0-480.0V, preferably 400.0-450.0V; the current is 8.0-20.0A, preferably 10.0-15.0A; the power is 1.0-5.0Kw, preferably 1.5-3.5Kw.
[0145] Particularly, the atmosphere in the sputtering chamber during the plating process of the nineteenth nickel-chromium alloy layer is argon.
[0146] Particularly, the argon gas flow rate is 750 sc / cm.
[0147] In particular, during the plating process of the second zinc oxide aluminum alloy film layer in step 3), the magnetron sputtering voltage is 430.0-530.0V, preferably 450.0-500.0V; the current is 30.0-70.0A, preferably 40.0-55.0A; the power is 10.0-35.0Kw, preferably 12.0-30.0Kw.
[0148] Particularly, the atmosphere in the sputtering chamber during the plating process of the twentieth zinc oxide aluminum alloy film layer is a mixed gas of argon and oxygen.
[0149] In particular, the volume ratio of argon to oxygen in the atmosphere is 16:1.
[0150] In particular, the flow rate of argon gas is 800 sc / cm, and the flow rate of oxygen gas is 50 sc / cm.
[0151] In particular, the 21st silicon-aluminum alloy film layer in step 3) is plated four times.
[0152] Wherein, during the first plating process, the vacuum magnetron sputtering voltage is 410.0-510.0V, preferably 450.0-490.0V; the current is 90.0-150.0A, preferably 100.0-130.0A; the power is 25.0-70.0Kw, preferably 35.0-55.0kW;
[0153] During the second plating process, the vacuum magnetron sputtering voltage is 400.0-500.0V, preferably 425.0-470.0V; the current is 80.0-130.0A, preferably 95.0-120.0A; the power is 30.0-70.0Kw, preferably 40.0-52.0kW;
[0154] During the third plating process, the vacuum magnetron sputtering voltage is 410.0-510.0V, preferably 420.0-490.0V; the current is 90.0-150.0A, preferably 100.0-130.0A; the power is 25.0-70.0Kw, preferably 35.0-55.0kW;
[0155] During the fourth plating process, the vacuum magnetron sputtering voltage is 400.0-500.0V, preferably 425.0-470.0V; the current is 80.0-130.0A, preferably 95.0-120.0A; and the power is 30.0-70.0Kw, preferably 35.0-52.0kW.
[0156] Particularly, the atmospheres during the first, second, third and fourth plating processes of the twenty-first silicon aluminum alloy film layer are argon and nitrogen.
[0157] In particular, the volume ratio of argon to nitrogen in the atmosphere during the first, second, third and fourth plating treatments of the twenty-first silicon aluminum alloy film layer is 2:3.
[0158] In particular, the flow rate of the argon gas is 400 sc / cm; the flow rate of the nitrogen gas is 600 sc / cm.
[0159] In particular, in step 3), the second zirconium oxide film layer is plated twice.
[0160] Among them, during the first plating process, the vacuum magnetron sputtering voltage is 380.0~460.0V, preferably 410.0~440.0V; the current is 20.0~50.0A, preferably 25.0~45.0A; the power is 5.0~40.0Kw, preferably 10.0~25.0kW; during the second plating process, the vacuum magnetron sputtering voltage is 380.0~460.0V, preferably 400.0~450.0V; the current is 20.0~60.0A, preferably 30.0~50.0A; the power is 8.0~40.0Kw, preferably 10.0~20.0kW.
[0161] Particularly, the atmosphere in the magnetron sputtering chamber during the first and second coating processes of the twenty-second zirconium oxide film layer is argon and oxygen.
[0162] In particular, the volume ratio of argon to oxygen in the atmosphere is 16:1.
[0163] In particular, the flow rate of the argon gas is 800 sc / cm; the flow rate of the nitrogen gas is 50 sc / cm.
[0164] In particular, it also includes step 3A) buffer treatment, which is to transport the coated glass from the vacuum magnetron sputtering chamber to the pressure buffer chamber, gradually increase the pressure in the buffer chamber until it reaches normal pressure; and reduce the temperature in the buffer chamber to 20-35°C.
[0165] Before the tempering treatment, the coated glass is subjected to a buffering treatment. The coated glass is transported from the vacuum magnetron sputtering chamber to the pressure buffer chamber, and the pressure in the buffer chamber is gradually increased until it reaches normal pressure; the temperature in the buffer chamber is lowered until it reaches room temperature (usually 20-35°C), and then the tempering treatment is performed.
[0166] Wherein, in the tempering process described in step 4), the heating time is controlled to be 400-500s; the temperature of the tempering heating furnace is 630-710°C; the temperature of the upper part of the glass in the heating furnace is 650-695°C and the temperature of the lower part is 630-680°C.
[0167] In particular, in the tempering process described in step 4), the quenching wind pressure in the quenching and quenching treatment of the glass is controlled to be greater than 2500Pa; and the cooling wind pressure after the quenching treatment is controlled to be 1000-2000Pa.
[0168] In particular, during the tempering process in step 4), the heating time is controlled to be 400 to 500 seconds, preferably 400 to 460 seconds;
[0169] Before entering the tempering furnace for tempering treatment, the coated glass needs to be preheated in a preheating furnace, wherein the temperature in the preheating furnace is 430-500°C, preferably 450-475°C; the convection ratio of the upper and lower hot air in the preheating furnace is 80-100%; the hot air temperature in the preheating furnace is 430-500°C, preferably 450-475°C; the glass preheating time is 200-250s, preferably 200-230s.
[0170] The temperature of the heating furnace is 630-710°C, preferably 630-680°C; the temperature of the upper part of the glass in the heating furnace is 650-695°C, and the lower part is 630-680°C; the heating time in the heating furnace is 200-250s, preferably 200-230s.
[0171] After the heating treatment, the glass is subjected to a rapid cooling treatment, i.e., a quenching treatment, wherein the rapid cooling wind pressure is greater than 2500Pa, preferably 2500-3800Pa; the quenching treatment speed is 350-500 (mm / s); the cooling wind pressure is 1000-2000Pa, preferably 1200-1800Pa; the wind grid is corrected to 40-50mm; the height from the upper wind nozzle to the upper surface of the glass is 25-40mm, preferably 30mm; the height from the lower wind nozzle to the lower surface of the glass is 30-45mm, preferably 35mm.
[0172] In particular, the tempering treatment may be performed off-site or on-site.
[0173] After the glass comes out of the heating of the tempering furnace, a fan is used to blow the glass to quickly cool the glass and form stress, that is, the glass is quenched, wherein the rapid cooling wind pressure during the quenching process is greater than 2500 Pa, preferably 2500-3800 Pa. After the quenching treatment, conventional cooling wind is used to blow the glass to reduce the glass temperature to room temperature, and the cooling wind pressure is 1000-2000 Pa, preferably 1200-1800 Pa.
[0174] The light blue tempered glass of the present invention is of high quality, is light blue in sunlight, and has good decorative effect; compared with single silver, double silver, and triple silver Low-E glass products, it has high visible light transmittance, low outdoor visible light reflectance, low solar energy transmittance, and high solar energy reflectance; and the low-emissivity coated tempered glass of the present invention has low heat transfer coefficient, low sunshade coefficient, and good thermal performance, and can effectively prevent heat energy from entering the room, thereby reducing refrigeration energy consumption; it can also be made into hollow glass, and has better light control and energy-saving effects; and after using the coated glass of the present invention, the building energy-saving design standard is reduced by more than 60-75% on the original basis.
[0175] The light blue tempered glass of the present invention is a functional triple-silver low-emissivity coated tempered glass, which has the following advantages and benefits compared with the prior art:
[0176] 1. The low-radiation coated tempered glass of the present invention is light blue, and is obtained by coating 22 layers of composite metal film layers on the surface of the glass in a vacuum state by magnetron sputtering, and then performing a tempering treatment. The composite metal film on the surface of the prepared tempered coated glass appears light blue under outdoor sunlight. The three-silver tempered low-radiation coated glass prepared by using inexpensive silicon-aluminum alloy, zinc-aluminum alloy, nickel-chromium alloy, silver, zinc-tin alloy, and zirconium oxide as target materials and ordinary colorless transparent float glass substrate has a low production cost, which is conducive to the promotion and use of the three-silver tempered low-radiation glass and is conducive to energy conservation and emission reduction of buildings.
[0177] The metallic silver film layer of the coated glass of the present invention is a functional layer, which is mainly used to reduce the emissivity, adjust the color and transmittance. When the thickness of each layer of silver is different, the color of the glass will change. Each film layer of the coated glass of the present invention absorbs heat and reflects heat, and the heat absorption and reflection of each film layer are different. The synergistic effect affects the color and optical and thermal properties of the coated glass product and the glass quality of the film layer. The coated glass of the present invention is light blue after reflection and interference of three layers of functional silver film layers.
[0178] The color of the coated glass seen from the front and from the side does not change much. Due to the interference of multiple silver film layers in the coated glass, the colors of the front and side of the coated glass will be affected, especially the interference on the side is the largest, resulting in inconsistency between the color of the side of the glass and the color of the front, resulting in obvious visual differences. The present invention uses a zinc oxide tin film layer to absorb the reflection of the third layer of silver, so that the interference of the third layer of silver on the color is minimized, thereby meeting the coordination of product performance and color; and the present invention uses other film layers to adjust the color of the coated glass to avoid the reddish or bluish color of the coated glass due to the reflection and interference of the silver film layer.
[0179] In the low-emissivity coated tempered glass of the present invention, a zinc tin oxide film layer is plated between the second and third silver film layers to play the role of absorption, isolation and bonding; it absorbs the reflection of the silver film layer and reduces the interference of the functional film layer silver film layer on the glass color.
[0180] 2. The reflective color of the low-emissivity coated tempered glass for near-zero energy consumption buildings of the present invention is light blue, which is the appearance color currently appreciated by designers or owners in the construction industry. Its main visual physical parameters are the transmittance color value of 80≤L * ≤90, -10≤a * ≤-5, -3≤b * ≤3; reflective color value is 28≤L * ≤35,0≤a * ≤5, -15≤b * ≤-8. It is light blue outdoors, colorful, bright and beautiful, and can be widely used in various buildings with good decorative effects.
[0181] 3. The optical performance technical parameter values of the low-emissivity coated tempered glass of the present invention meet the standards of GB / T18915.1-2013 "Coated Glass Part 2: Low-emissivity Coated Glass", its visible light transmittance is greatly improved, and the maximum value of the color index change is less than 1.2%; the color uniformity is high, less than 2.0CIELAB.
[0182] 4. The light blue tempered glass of the present invention can be made into conventional insulating glass (taking the structure of 6 triple silver low-emissivity coated tempered glass (glass) + 12-Ar + 6-glass (white glass) as an example), which is suitable for creating a bright and comfortable indoor and outdoor light environment; the visible light transmittance is greater than 62%, and the outdoor visible light reflectance is less than 11.3%; the solar energy transmittance is less than 26%; the total solar energy transmittance is less than 29%; the outdoor solar energy reflectance is higher than 39%, and the energy-saving effect is obvious.
[0183] The heat transfer coefficient of the low-emissivity coated tempered glass of the present invention is lower than 1.34W / m in winter. 2 ·K,; lower than 1.23W / m in summer 2 K; shading coefficient (Sc) less than 0.33; relative heat gain less than 219w / m 2 It has good thermal performance, can effectively block the radiation of sunlight heat into the room, has good energy-saving performance, reduces refrigeration energy consumption, and has better light control and energy-saving effects.
[0184] 5. The three-glass two-chamber insulating glass (with a structure of 6-triple silver tempered low-emissivity coated glass (glass) + 12-Ar + 6-glass (white glass) + 12-Ar + 6-glass (white glass)) made of the low-emissivity coated tempered glass of the present invention has a visible light transmittance greater than 56%; outdoor visible light reflectivity is less than 15%; solar energy transmittance is less than 23.1%; solar energy outdoor reflectivity is higher than 40%; it is suitable for creating a bright and comfortable indoor and outdoor light environment; at the same time, its heat transfer coefficient is less than 1.02W / m in winter 2 K, lower than 1.01W / m in summer 2 K; shading coefficient (Sc) less than 0.3; total solar transmittance less than 26%, relative heat gain less than 198w / m 2 It has good thermal performance, can effectively block the radiation of sunlight heat into the room, has good energy-saving performance, reduces refrigeration energy consumption, and has better light control and energy-saving effects.
[0185] The building with the low-emissivity coated tempered glass of the present invention can meet the standards and requirements for glass performance in GB 55015-2021 "General Specification for Energy Conservation and Renewable Energy Utilization in Buildings".
[0186] 6. The light blue tempered glass of the present invention can be made into triple-silver low-emissivity coated glass with different optical and thermal properties by changing the thickness of each coating layer during the preparation process, and can also be made into different types of insulating glass to meet different market demands.
[0187] 7. The light blue tempered glass of the present invention realizes color change on colorless transparent white glass, has low cost, is convenient and reliable.
[0188] In the light blue tempered glass of the present invention, the first silicon aluminum layer stacked on the tempered glass substrate plays a role of being closely bonded to the original glass sheet, the second zinc oxide aluminum film layer plays a role of paving and adjusting the transmittance; the third nickel chromium film layer adjusts the brightness and protects the silver film layer; the three silver film layers are coordinated to make the outdoor color of the glass reach the required light blue effect, the indoor color reach a neutral color, and coordinate the lateral color of the three silver glasses, the thickness of the first and third silver layers in the present invention is basically the same, and the thickness of the second silver layer is less than the thickness of the first silver layer, the thickness deviation between the first and third silver layers is controlled within 0.5nm, the difference between the thickness of the second silver layer and the thickness of the first and third silver layers is between 1.5-2.6nm, the front color of the glass is light blue, and the deviation of the front and side reflection colors of the glass is within ±1Lab*, if the thickness allowable deviation of the first and third silver layers exceeds 1nm, the front color and side color deviation of the glass exceed the national standard range (greater than 2.5Lab * The zinc tin oxide of the present invention absorbs the reflection of the third layer of silver to reduce interference; the silicon aluminum and zirconium oxide on the top of the film layer are the top protective layer, which mainly protects each film layer from being scratched during the processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0189] Figure 1 It is a cross-sectional schematic diagram of the light blue tempered glass of the present invention.
[0190] Description of reference numerals:
[0191] 1. tempered glass substrate; 2. first silicon-aluminum alloy film layer; 3. second zinc-oxide-aluminum alloy film layer; 4. third nickel-chromium alloy film layer; 5. fourth silver film layer; 6. fifth nickel-chromium alloy film layer; 7. sixth zinc-oxide-aluminum alloy film layer; 8. seventh silicon-aluminum alloy film layer; 9. eighth zinc-oxide-aluminum alloy film layer; 10. ninth nickel-chromium alloy film layer; 11. tenth silver film layer; 12. eleventh nickel-chromium alloy film layer; 13. twelfth zinc-oxide-aluminum alloy film layer; 14. thirteenth silicon-aluminum alloy film layer; 15. fourteenth zinc-tin oxide film; 16. fifteenth silicon-aluminum alloy film; 17. sixteenth zinc-oxide-aluminum alloy film; 18. seventeenth nickel-chromium alloy film; 19. eighteenth silver film; 20. nineteenth nickel-chromium alloy film; 21. twentieth zinc-oxide-aluminum alloy film; 22. twenty-first silicon-aluminum alloy film; 23. twenty-second zirconium oxide film. DETAILED DESCRIPTION
[0192] The present invention will be further described below by way of examples, and the advantages and features of the present invention will become clearer as the description proceeds. However, these examples are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0193] like Figure 1The high-quality light blue tempered glass for near-zero energy consumption buildings of the present invention comprises, in sequence, a tempered glass substrate 1, a first silicon-aluminum alloy film layer 2; a second zinc-oxide aluminum alloy film layer 3; a third nickel-chromium alloy film layer 4; a fourth silver film layer 5; a fifth nickel-chromium alloy film layer 6, a sixth zinc-oxide aluminum alloy film layer 7, a seventh silicon-aluminum alloy film layer 8; an eighth zinc-oxide aluminum alloy film layer 9; a ninth nickel-chromium alloy film layer 10; a tenth silver film layer 11; an eleventh nickel-chromium alloy film layer 12; a twelfth zinc-oxide aluminum alloy film layer 13; a thirteenth silicon-aluminum alloy film layer 14; a fourteenth zinc-oxide-tin alloy film 15; a fifteenth silicon-aluminum alloy film 16; a sixteenth zinc-oxide aluminum alloy film 17; a seventeenth nickel-chromium alloy film 18; an eighteenth silver film 19; a nineteenth nickel-chromium alloy film 20; The twentieth zinc oxide aluminum alloy film 20; the twenty-first silicon aluminum alloy film 22; the twenty-second zirconium oxide film 23; wherein: the thickness of the first silicon aluminum alloy film layer is 55.0-65.0nm, preferably 55.3-61.7nm, and more preferably 59-60.7nm; the thickness of the second zinc oxide aluminum alloy film layer is 10.0-30.0nm, preferably 15.0-25.0nm, and more preferably 20-20.5nm; the thickness of the third nickel chromium alloy layer is 0.5-3.0nm, preferably 1.0-2.0nm, and more preferably 1.4-1.6nm; the thickness of the fourth silver film layer is 8.0-15.0nm, preferably 10.0-13.0nm, and more preferably 1 The thickness of the fifth nickel-chromium alloy film layer is 0.5-3.0 nm, preferably 1.0-2.0 nm, and more preferably 1.4-1.7 nm; the thickness of the sixth zinc-aluminum alloy film layer is 15.0-25.0 nm, preferably 18.0-23 nm, and more preferably 21.0-22.7 nm; the thickness of the seventh silicon-aluminum alloy film layer is 300.0-420.0 nm, preferably 320.0-350.0 nm, and more preferably 335-336 nm; the thickness of the eighth zinc-aluminum alloy film layer is 15.0-25.0 nm, preferably 15-22.0 nm, and more preferably 18.8-20.0 nm; the thickness of the ninth nickel-chromium alloy film layer is 10.0-15.0 nm, preferably 11.0-12.0 nm, and more preferably 18.8-20.0 nm; the thickness of the ninth nickel-chromium alloy film layer is 15.0-25.0 nm, preferably 15-22.0 nm, and more preferably 18.8-20.0 nm. The thickness of the tenth silver film layer is 1.0-5.0nm, preferably 2.0-4.0nm, and more preferably 2.8-3.0nm; the thickness of the tenth silver film layer is 5.0-15.0nm, preferably 8.0-10.0nm, and more preferably 9.2-9.3nm; the thickness of the eleventh nickel-chromium alloy film layer is 1.5-3.5nm, preferably 1.5-2.5nm, and more preferably 1.7-1.8nm; the thickness of the twelfth zinc oxide aluminum alloy film layer is 15.0-50.0nm, preferably 20.0-35.0nm, and more preferably 30-30.5nm; the thickness of the thirteenth silicon aluminum alloy film layer is 130.0-200.0nm, and preferably 140.0-170.0nm, more preferably 159-160nm; the thickness of the fourteenth zinc oxide tin alloy film layer is 15.0-40.0nm, preferably 20.0-35.0nm, more preferably 30-30.4nm; the thickness of the fifteenth silicon aluminum alloy film layer is 110.0-150.0nm, preferably 114-128.0nm, more preferably 124-128nm; the thickness of the sixteenth zinc oxide aluminum alloy film layer is 15.0-30.0nm, preferably 17.0-25.0nm, more preferably 19.5-20.5nm; the thickness of the seventeenth nickel chromium alloy film layer is 1.0-3.0nm, preferably 1.5-2.5nm, more preferably 2.0-2.1nm; the thickness of the eighteenth silver film layer is 8.0-1 5.0nm, preferably 10.0-13.0nm, more preferably 11.3-11.5nm; the thickness of the nineteenth nickel-chromium alloy film layer is 1.0-3.0nm, preferably 1.5-2.5nm, more preferably 2.0-2.1nm; the thickness of the twentieth zinc oxide aluminum alloy film layer is 10.0-30.0nm, preferably 15.0-25.0nm, more preferably 19-21nm; the thickness of the twenty-first silicon aluminum alloy film layer is 150.0-180.0nm, preferably 155.0-170.0nm, more preferably 160-166nm; the thickness of the twenty-second zirconium oxide alloy film layer is 10.0-50.0nm, preferably 20.0-35.0nm, more preferably 24-26nm. .
[0194] Example 1
[0195] 1. Target sintering
[0196] In the 1st to 39th target chambers (magnetron sputtering chambers) of a vacuum magnetron sputtering coating machine, the pre-pressed target materials are sintered on the corresponding target positions, wherein:
[0197] The silicon-aluminum alloy target is sintered on the target positions of the 1st-2nd, 8th-13th, 21st-24th, 27th-28th, and 34th-37th magnetron sputtering chambers. The sintering purity of the silicon-aluminum alloy target is ≥99.5% and the density is ≥2.1g / cm 3 , the melting point is 580℃, the Al content is 8-12±2wt%, and the rest is Si; the sintering time of silicon aluminum alloy is 90min;
[0198] Zinc oxide aluminum targets were sintered on the target positions of the 3rd, 7th, 14th-15th, 19th-20th, 29th and 33rd magnetron sputtering chambers. The sintering purity of zinc oxide aluminum targets was ≥99.90% and the theoretical density was 5.56 g / cm 3 ((ZnO)-2wt%(Al2O3)), target density ≥5.50g / cm 3, relative density ≥ 99%, composed of 2wt% Al2O3 and 98wt% ZnO; the sintering time of zinc oxide aluminum alloy is 60min;
[0199] The nickel-chromium alloy targets were sintered on the target positions of the 4th, 6th, 16th, 18th, 30th and 32nd magnetron sputtering chambers. The sintering purity of the nickel-chromium alloy targets was ≥99.7%, the theoretical density was 8.49 (Ni-20%Cr), and the target density was ≥8.5g / cm 3 , relative density ≥ 98%, melting point 1420℃, Cr content 20±1wt%, the rest Ni; sintering time of nickel-chromium alloy is 90min;
[0200] Silver targets were sintered on the target positions of the 5th, 17th and 31st magnetron sputtering chambers. The sintering purity of the silver targets was ≥99.99% and the theoretical density was ≥10.49 g / cm 3 , target density is ≥10.28g / cm 3 , relative density ≥ 98%, melting point 960℃; sintering time of silver is 60min;
[0201] The zinc tin oxide target is sintered on the target position of the 25th-26th magnetron sputtering chamber. The sintering purity of the zinc tin oxide target is ≥99.9%, the Sn content is (50±2)wt% and the rest is Sn, and the density is ≥7.1g / cm 3 , zinc oxide tin alloy with a melting point of 360°C; the sintering time of zinc oxide tin alloy is 90 minutes;
[0202] The zirconium oxide target material is sintered on the target position of the 38th-39th magnetron sputtering chamber. The sintering purity of the zirconium oxide target material is ≥99.9% and the density is ≥5.35g / cm 3 , the melting point is 2300℃; the sintering time of oxide pick is 90min.
[0203] The silicon aluminum alloy used in the present invention meets the composition requirements of silicon aluminum targets in the national standard JC / T2068-2011; the nickel-chromium alloy meets the composition requirements of nickel-chromium targets in the national standard JC / T2068-2011; the zinc oxide aluminum alloy meets the composition requirements of zinc oxide aluminum targets in the national standard JC / T2068-2011; the silver meets the composition requirements of silver targets in the national industry standard JC / T2068-2011; the zinc oxide tin alloy meets the composition requirements of zinc oxide tin alloy targets in the national industry standard JC / T2068-2011; and the zirconium oxide meets the composition requirements of zirconium oxide targets in the national industry standard JC / T2068-2011.
[0204] 2. Clean the glass
[0205] 2A) Place a 6.0 mm thick float glass sheet in a glass coating cleaning machine (GTA, Germany, model: GTA01-M) at a temperature of 37°C and a mineral content of ≤5μ / cm / m 2 Deionized water is used for cleaning at a speed of 5 m / min;
[0206] In addition to the float glass with a thickness of 6 mm, the glass sheets of other thicknesses are also suitable for the present invention. Using deionized water to wash the glass can not only remove the oil or other impurities on the glass surface, but also avoid the problem of introducing other metal ions when washing with tap water.
[0207] 2B) Drying the cleaned float glass at 20-50° C. at a drying speed of 5 m / min to remove water droplets on the glass surface to obtain a dry glass sheet.
[0208] 3. Dehumidification and degassing treatment
[0209] 3A) The dry glass original sheet is conveyed to the first vacuum chamber of the vacuum magnetron sputtering coating machine by a conveying roller, and the dry glass original sheet is subjected to the first dehumidification and degassing treatment, wherein the first dehumidification and degassing treatment time is 30s, the transmission speed is 5m / min; the first dehumidification and degassing treatment temperature is -140℃, and the absolute pressure is 5.0×10 -2 Below mbar;
[0210] 3B) The dry glass sheet after the first dehumidification and degassing treatment is transported to the second vacuum chamber for the second dehumidification and degassing treatment. The second dehumidification and degassing treatment takes 30 seconds and the transmission speed is 5 m / min. The temperature of the second dehumidification and degassing treatment is 20-60°C and the absolute pressure is 3.5×10 -5 mbar or less, the glass to be coated is obtained;
[0211] In the present invention, the glass transmission speed is described by taking 5 m / min as an example, and the glass transmission speed of 2 to 10 m / min is also applicable to the present invention.
[0212] 4. Coating treatment
[0213] 4A) Turn on the power of the sputtering chamber of the vacuum magnetron sputtering coating machine and heat it to make the temperature in the sputtering chamber (including the first to the 39th target chambers) of the vacuum magnetron sputtering coating machine reach 20-60°C and the absolute pressure decrease to 2.0-4.0×10 -5 mbar or less (the absolute pressure in the present invention is 3.0×10 -5 mbar is used as an example below), and the glass to be coated is subjected to magnetron sputtering coating treatment from the 1st target chamber to the 39th target chamber in sequence;
[0214] 4B) The glass to be coated obtained after two dehumidification and degassing treatments is sequentially sent into the 5th target chamber to the 39th target chamber of the coating sputtering chamber at a conveying speed of 5 m / min, and subjected to coating treatment to obtain coated glass. The process parameters are shown in Table 1, wherein:
[0215] The original glass sheet to be coated is subjected to the first coating treatment in the first target chamber, that is, the first coating treatment of the first silicon-aluminum alloy film is carried out. The magnetron sputtering process conditions of the first coating are shown in Table 1. The metal atoms of the silicon-aluminum alloy target material sintered on the target position of the first target chamber are sputtered from the surface of the target material and deposited on the surface of the original float glass sheet. The thickness of the alloy film layer of the first coating is controlled to be 30.0 nm, and the first coated glass is obtained.
[0216] The first coated glass is subjected to a second coating treatment in the second target chamber, that is, a second coating treatment of the first silicon-aluminum alloy film is carried out. The magnetron sputtering process conditions for the second coating are shown in Table 1. The metal atoms of the silicon-aluminum alloy target material sintered on the target position of the second target chamber are sputtered from the surface of the target material and deposited on the surface of the first coated glass. The thickness of the alloy film layer of the second coating is controlled to be 30.0nm, and the second coated glass is obtained. At this point, the coating of the first silicon-aluminum alloy film layer is completed, and the thickness of the first silicon-aluminum alloy film layer is 60nm.
[0217] The second coated glass is subjected to a third coating treatment in the third target chamber, i.e., a second zinc oxide aluminum alloy film is plated. The magnetron sputtering process conditions for the third coating are shown in Table 1. The metal atoms of the zinc oxide aluminum alloy target material sintered on the target position in the third target chamber are sputtered from the surface of the target material and deposited on the surface of the second coated glass. The thickness of the alloy film layer plated for the third time is controlled to be 20.0 nm, and the third coated glass is obtained. At this point, the second zinc oxide aluminum alloy film layer is plated, and the thickness of the second zinc oxide aluminum alloy film layer is 20 nm.
[0218] The third coated glass is subjected to a fourth coating treatment in the fourth target chamber, i.e., a third nickel-chromium alloy film is plated. The magnetron sputtering process conditions for the fourth plating are shown in Table 1. The metal atoms of the nickel-chromium alloy target material sintered on the target position in the fourth target chamber are sputtered from the surface of the target material and deposited on the surface of the third coated glass. The thickness of the alloy film layer plated for the fourth time is controlled to be 1.50 nm, and the fourth coated glass is obtained. At this point, the plating of the third nickel-chromium alloy film layer is completed, and the thickness of the third nickel-chromium alloy film layer is 1.5 nm.
[0219] The fourth coated glass is subjected to a fifth coating treatment in the fifth target chamber, that is, a fourth silver film is plated. The magnetron sputtering process conditions for the fifth coating are shown in Table 1. The metal atoms of the silver target material sintered on the target position in the fifth target chamber are sputtered from the surface of the target material and deposited on the surface of the fourth coated glass. The thickness of the metal film layer plated for the fifth time is controlled to be 11.80 nm, and the fifth coated glass is obtained. At this point, the coating of the fourth silver film layer is completed, and the thickness of the fourth silver film layer is 11.80 nm.
[0220] The fifth coated glass is subjected to a sixth coating treatment in the sixth target chamber, i.e., a fifth nickel-chromium alloy film is plated. The magnetron sputtering process conditions for the sixth plating are shown in Table 1. The metal atoms of the nickel-chromium alloy target material sintered on the target position of the sixth target chamber are sputtered from the surface of the target material and deposited on the surface of the fifth coated glass. The thickness of the alloy film layer plated for the sixth time is controlled to be 1.60 nm, and the sixth coated glass is obtained. At this point, the plating of the fifth nickel-chromium alloy film layer is completed, and the thickness of the fifth nickel-chromium alloy film layer is 1.60 nm.
[0221] The sixth coated glass was subjected to a seventh coating treatment in the seventh target chamber, that is, a sixth zinc oxide aluminum alloy film was plated. The magnetron sputtering process conditions for the seventh coating are shown in Table 1. The metal atoms of the zinc oxide aluminum alloy target material sintered on the target position of the seventh target chamber were sputtered from the surface of the target material and deposited on the surface of the sixth coated glass. The thickness of the alloy film layer plated for the seventh time was controlled to be 21.0 nm, and the seventh coated glass was obtained. At this point, the coating of the sixth zinc oxide aluminum alloy film layer was completed, and the thickness of the sixth zinc oxide aluminum alloy film layer was 21.0 nm.
[0222] The seventh coated glass is subjected to the eighth coating treatment in the eighth target chamber, that is, the first coating treatment of the seventh silicon-aluminum alloy film is carried out, and the magnetron sputtering process conditions of the eighth coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the eighth target chamber are sputtered from the surface of the target material and deposited on the surface of the seventh coated glass, and the thickness of the alloy film layer of the eighth coating is controlled to be 65.0 nm, so as to obtain the eighth coated glass;
[0223] The eighth coated glass is subjected to a ninth coating treatment in the ninth target chamber, that is, the seventh silicon-aluminum alloy film is subjected to a second coating treatment, and the magnetron sputtering process conditions for the ninth coating are shown in Table 1; metal atoms of the silicon-aluminum alloy target material sintered on the target position of the ninth target chamber are sputtered from the surface of the target material and deposited on the surface of the eighth coated glass, and the thickness of the alloy film layer of the ninth coating is controlled to be 65.0 nm, thereby obtaining a ninth coated glass;
[0224] The ninth coated glass is subjected to the tenth coating treatment in the tenth target chamber, that is, the seventh silicon-aluminum alloy film is subjected to the third coating treatment, and the magnetron sputtering process conditions of the tenth coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the tenth target chamber are sputtered from the surface of the target material and deposited on the surface of the ninth coated glass, and the thickness of the alloy film layer of the tenth coating is controlled to be 65.0 nm, so as to obtain the tenth coated glass;
[0225] The tenth coated glass is subjected to an eleventh coating treatment in the eleventh target chamber, that is, the seventh silicon-aluminum alloy film is subjected to the fourth coating treatment, and the magnetron sputtering process conditions for the eleventh coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the eleventh target chamber are sputtered from the surface of the target material and deposited on the surface of the tenth coated glass, and the thickness of the alloy film layer coated for the eleventh time is controlled to be 25.0 nm, thereby obtaining the eleventh coated glass;
[0226] The eleventh coated glass is subjected to the twelfth coating treatment in the twelfth target chamber, that is, the fifth coating treatment of the seventh silicon-aluminum alloy film is carried out, and the magnetron sputtering process conditions of the twelfth coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the twelfth target chamber are sputtered from the surface of the target material and deposited on the surface of the eleventh coated glass, and the thickness of the alloy film layer of the twelfth coating is controlled to be 65.0 nm, so as to obtain the twelfth coated glass;
[0227] The twelfth coated glass is subjected to the thirteenth coating treatment in the 13th target chamber, that is, the sixth coating treatment of the seventh silicon-aluminum alloy film is subjected to the magnetron sputtering process conditions for the thirteenth coating as shown in Table 1; metal atoms of the silicon-aluminum alloy target material sintered on the target position in the 13th target chamber are sputtered from the surface of the target material and deposited on the surface of the twelfth coated glass, and the thickness of the alloy film layer coated for the thirteenth time is controlled to be 50.0nm, thereby obtaining the thirteenth coated glass; so far, the coating of the seventh silicon-aluminum alloy film layer is completed, and the thickness of the seventh silicon-aluminum alloy film layer is 335nm.
[0228] The thirteenth coated glass is subjected to the fourteenth coating treatment in the fourteenth target chamber, that is, the first coating treatment of the eighth zinc oxide aluminum alloy film is carried out, and the magnetron sputtering process conditions of the fourteenth coating are shown in Table 1; the metal atoms of the zinc oxide aluminum alloy target material sintered on the target position of the fourteenth target chamber are sputtered from the surface of the target material and deposited on the surface of the thirteenth coated glass, and the thickness of the alloy film layer plated for the fourteenth time is controlled to be 9.5 nm, so as to obtain the fourteenth coated glass;
[0229] The fourteenth coated glass is subjected to the fifteenth coating treatment in the fifteenth target chamber, that is, the second coating treatment of the eighth zinc oxide aluminum alloy film is carried out, and the magnetron sputtering process conditions for the fifteenth coating are shown in Table 1; the metal atoms of the zinc oxide aluminum alloy target material sintered on the target position of the fifteenth target chamber are sputtered from the surface of the target material and deposited on the surface of the fourteenth coated glass, and the thickness of the alloy film layer plated for the fifteenth time is controlled to be 9.5nm, so as to obtain the fifteenth coated glass; so far, the coating of the eighth zinc oxide aluminum alloy film layer is completed, and the thickness of the eighth zinc oxide aluminum alloy film layer is 19nm.
[0230] The fifteenth coated glass is subjected to the sixteenth coating treatment in the sixteenth target chamber, that is, the ninth nickel-chromium alloy film is plated. The magnetron sputtering process conditions for the sixteenth plating are shown in Table 1. The metal atoms of the nickel-chromium alloy target material sintered on the target position of the sixteenth target chamber are sputtered from the surface of the target material and deposited on the surface of the fifteenth coated glass. The thickness of the alloy film layer plated for the sixteenth time is controlled to be 2.9 nm, and the sixteenth coated glass is obtained. At this point, the plating of the ninth nickel-chromium alloy film layer is completed, and the thickness of the ninth nickel-chromium alloy film layer is 2.9 nm.
[0231] The sixteenth coated glass was subjected to the seventeenth coating treatment in the seventeenth target chamber, that is, the tenth silver film was plated. The magnetron sputtering process conditions for the seventeenth coating are shown in Table 1. The metal atoms of the silver target material sintered on the target position of the seventeenth target chamber were sputtered from the surface of the target material and deposited on the surface of the sixteenth coated glass. The thickness of the metal film layer of the seventeenth coating was controlled to be 9.2 nm, and the seventeenth coated glass was obtained. At this point, the tenth silver film layer was plated and the thickness of the tenth silver film layer was 9.2 nm.
[0232] The seventeenth coated glass is subjected to the eighteenth coating treatment in the eighteenth target chamber, that is, the eleventh nickel-chromium alloy film is plated. The magnetron sputtering process conditions for the eighteenth plating are shown in Table 1. The metal atoms of the nickel-chromium alloy target material sintered on the target position of the eighteenth target chamber are sputtered from the surface of the target material and deposited on the surface of the seventeenth coated glass. The thickness of the alloy film layer plated for the eighteenth time is controlled to be 1.7 nm, and the eighteenth coated glass is obtained. At this point, the plating of the eleventh nickel-chromium alloy film layer is completed, and the thickness of the eleventh nickel-chromium alloy film layer is 1.7 nm.
[0233] The eighteenth coated glass is subjected to the nineteenth coating treatment in the nineteenth target chamber, that is, the first coating treatment of the twelfth zinc oxide aluminum alloy film is carried out, and the magnetron sputtering process conditions of the nineteenth coating are shown in Table 1; the metal atoms of the zinc oxide aluminum alloy target material sintered on the target position of the nineteenth target chamber are sputtered from the surface of the target material and deposited on the surface of the eighteenth coated glass, and the thickness of the alloy film layer plated for the nineteenth time is controlled to be 15.0 nm, so as to obtain the nineteenth coated glass;
[0234] The nineteenth coated glass was subjected to the twentieth coating treatment in the 20th target chamber, that is, the second coating treatment of the twelfth zinc oxide aluminum alloy film was carried out, and the magnetron sputtering process conditions for the twentieth coating were shown in Table 1; the metal atoms of the zinc oxide aluminum alloy target material sintered on the target position of the 20th target chamber were sputtered from the surface of the target material and deposited on the surface of the nineteenth coated glass, and the thickness of the alloy film layer plated for the twentieth time was controlled to be 15.0nm, and the twentieth coated glass was obtained; so far, the coating of the twelfth zinc oxide aluminum alloy film layer was completed, and the thickness of the twelfth zinc oxide aluminum alloy film layer was 30.0nm.
[0235] The 20th coated glass is subjected to the 21st coating treatment in the 21st target chamber, that is, the first coating treatment of the 13th silicon-aluminum alloy film is carried out, and the magnetron sputtering process conditions of the 21st coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the 21st target chamber are sputtered from the surface of the target material and deposited on the surface of the 20th coated glass, and the thickness of the alloy film layer coated for the 21st time is controlled to be 55.0nm, so as to obtain the 21st coated glass;
[0236] The twenty-first coated glass is subjected to a twenty-second coating treatment in the twenty-second target chamber, that is, the second coating treatment of the thirteenth silicon-aluminum alloy film is performed, and the magnetron sputtering process conditions of the twenty-second coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the twenty-second target chamber are sputtered from the surface of the target material and deposited on the surface of the twenty-first coated glass, and the thickness of the alloy film layer coated for the twenty-second time is controlled to be 25.0 nm, thereby obtaining the twenty-second coated glass;
[0237] The twenty-second coated glass is subjected to the twenty-third coating treatment in the twenty-third target chamber, that is, the third coating treatment of the thirteenth silicon-aluminum alloy film is carried out, and the magnetron sputtering process conditions of the twenty-third coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the twenty-third target chamber are sputtered from the surface of the target material and deposited on the surface of the twenty-second coated glass, and the thickness of the alloy film layer plated for the twenty-third time is controlled to be 55.0 nm, so as to obtain the twenty-third coated glass;
[0238] The twenty-third coated glass is subjected to the twenty-fourth coating treatment in the twenty-fourth target chamber, that is, the fourth coating treatment of the thirteenth silicon-aluminum alloy film is carried out, and the magnetron sputtering process conditions for the twenty-fourth coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the 24th target chamber are sputtered from the surface of the target material, and deposited on the surface of the twenty-third coated glass, and the thickness of the alloy film layer plated for the twenty-fourth time is controlled to be 25.0nm, and the twenty-fourth coated glass is obtained; so far, the coating of the thirteenth silicon-aluminum alloy film layer is completed, and the thickness of the thirteenth silicon-aluminum alloy film layer is 160nm.
[0239] The twenty-fourth coated glass is subjected to the twenty-fifth coating treatment in the twenty-fifth target chamber, that is, the first coating treatment of the fourteenth zinc oxide tin alloy film is carried out, and the magnetron sputtering process conditions of the twenty-fifth coating are shown in Table 1; the metal atoms of the zinc oxide tin alloy target material sintered on the target position of the twenty-fifth target chamber are sputtered from the surface of the target material and deposited on the surface of the twenty-fourth coated glass, and the thickness of the alloy film layer plated in the twenty-fifth coating is controlled to be 15.0 nm, thereby obtaining the twenty-fifth coated glass;
[0240] The twenty-fifth coated glass was subjected to the twenty-sixth coating treatment in the twenty-sixth target chamber, that is, the second coating treatment of the fourteenth zinc oxide tin alloy film was carried out, and the magnetron sputtering process conditions for the twenty-sixth coating were shown in Table 1; the metal atoms of the zinc oxide tin alloy target material sintered on the target position of the twenty-sixth target chamber were sputtered from the surface of the target material and deposited on the surface of the twenty-fifth coated glass, and the thickness of the alloy film layer plated for the twenty-fifth time was controlled to be 15.0 nm, and the twenty-sixth coated glass was obtained; so far, the plating of the fourteenth zinc oxide tin alloy film layer was completed, and the thickness of the fourteenth zinc oxide tin alloy film layer was 30.0 nm.
[0241] The zinc tin oxide film layer in the present invention plays the role of absorption, isolation and bonding in the film layer of the coated glass; if there is no zinc tin oxide layer, the coated glass of the present invention cannot be tempered; the outdoor reflection color of the glass changes greatly and the brightness is high; the zinc tin oxide can improve the bonding function of the third silver functional film layer, isolate far infrared, enhance the function of the third silver film, absorb the reflection brightness of the nickel chromium layer, and coordinate the color of the coated glass.
[0242] The twenty-sixth coated glass is subjected to the twenty-seventh coating treatment in the twenty-seventh target chamber, that is, the first coating treatment of the fifteenth silicon-aluminum alloy film is carried out, and the magnetron sputtering process conditions of the twenty-seventh coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the twenty-seventh target chamber are sputtered from the surface of the target material and deposited on the surface of the twenty-sixth coated glass, and the thickness of the alloy film layer coated for the twenty-seventh time is controlled to be 63.0 nm, thereby obtaining the twenty-seventh coated glass;
[0243] The twenty-seventh coated glass is subjected to the twenty-eighth coating treatment in the twenty-eighth target chamber, that is, the second coating treatment of the fifteenth silicon-aluminum alloy film is carried out, and the magnetron sputtering process conditions for the twenty-eighth coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the twenty-eighth target chamber are sputtered from the surface of the target material, and deposited on the surface of the twenty-seventh coated glass, and the thickness of the alloy film layer coated for the twenty-eighth time is controlled to be 63.0nm, to obtain the twenty-eighth coated glass; so far, the coating of the fifteenth silicon-aluminum alloy film layer is completed, and the thickness of the fifteenth silicon-aluminum alloy film layer is 126.0nm.
[0244] The twenty-eighth coated glass was subjected to the twenty-ninth coating treatment in the twenty-ninth target chamber, that is, the plating treatment of the sixteenth zinc oxide aluminum alloy film was carried out, and the magnetron sputtering process conditions for the twenty-ninth coating were shown in Table 1; the metal atoms of the zinc oxide aluminum alloy target material sintered on the target position of the 29th target chamber were sputtered from the surface of the target material, and deposited on the surface of the twenty-eighth coated glass, and the thickness of the alloy film layer plated for the twenty-ninth coating was controlled to be 20.0 nm, and the twenty-ninth coated glass was obtained; so far, the plating of the sixteenth zinc oxide aluminum alloy film layer was completed, and the thickness of the sixteenth zinc oxide aluminum alloy film layer was 20.0 nm.
[0245] The twenty-ninth coated glass was subjected to the thirtieth coating treatment in the 30th target chamber, that is, the seventeenth nickel-chromium alloy film was plated. The magnetron sputtering process conditions for the 30th plating are shown in Table 1. The metal atoms of the nickel-chromium alloy target material sintered on the target position of the 30th target chamber were sputtered from the surface of the target material and deposited on the surface of the twenty-ninth coated glass. The thickness of the alloy film layer plated for the 30th time was controlled to be 2.0 nm, and the 30th coated glass was obtained. At this point, the plating of the seventeenth nickel-chromium alloy film layer was completed, and the thickness of the seventeenth nickel-chromium alloy film layer was 2.0 nm.
[0246] The 30th coated glass is subjected to the 31st coating treatment in the 31st target chamber, that is, the 18th silver film is plated. The magnetron sputtering process conditions for the 31st coating are shown in Table 1. The metal atoms of the silver target material sintered on the target position of the 31st target chamber are sputtered from the surface of the target material and deposited on the surface of the 30th coated glass. The thickness of the metal film layer plated for the 31st time is controlled to be 11.3nm, and the 31st coated glass is obtained. At this point, the coating of the 18th silver film layer is completed, and the thickness of the 18th silver film layer is 11.3nm.
[0247] The thirty-first coated glass is subjected to the thirty-second coating treatment in the thirty-second target chamber, that is, the nineteenth nickel-chromium alloy film is plated. The magnetron sputtering process conditions for the thirty-second plating are shown in Table 1. The metal atoms of the nickel-chromium alloy target material sintered on the target position of the thirty-second target chamber are sputtered from the surface of the target material and deposited on the surface of the thirty-first coated glass. The thickness of the alloy film layer plated for the thirty-second time is controlled to be 2.1 nm, and the thirty-second coated glass is obtained. At this point, the plating of the nineteenth nickel-chromium alloy film layer is completed, and the thickness of the nineteenth nickel-chromium alloy film layer is 2.1 nm.
[0248] The thirty-second coated glass is subjected to the thirty-third coating treatment in the thirty-third target chamber, that is, the coating treatment of the twentieth zinc oxide aluminum alloy film is carried out, and the magnetron sputtering process conditions of the thirty-third coating are shown in Table 1; the metal atoms of the zinc oxide aluminum alloy target material sintered on the target position of the 33rd target chamber are sputtered from the surface of the target material, and deposited on the surface of the thirty-second coated glass, and the thickness of the alloy film layer plated for the thirty-third time is controlled to be 20.0nm, and the thirty-third coated glass is obtained; so far, the coating of the twentieth zinc oxide aluminum alloy film layer is completed, and the thickness of the twentieth zinc oxide aluminum alloy film layer is 20.0nm.
[0249] The thirty-third coated glass is subjected to the thirty-fourth coating treatment in the thirty-fourth target chamber, that is, the first coating treatment of the twenty-first silicon-aluminum alloy film is performed, and the magnetron sputtering process conditions of the thirty-fourth coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the thirty-fourth target chamber are sputtered from the surface of the target material and deposited on the surface of the thirty-third coated glass, and the thickness of the alloy film layer coated for the thirty-fourth time is controlled to be 42.0 nm, thereby obtaining the thirty-fourth coated glass;
[0250] The thirty-fourth coated glass is subjected to the thirty-fifth coating treatment in the thirty-fifth target chamber, that is, the second coating treatment of the twenty-first silicon-aluminum alloy film is performed, and the magnetron sputtering process conditions of the thirty-fifth coating are shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the thirty-fifth target chamber are sputtered from the surface of the target material and deposited on the surface of the thirty-fourth coated glass original sheet, and the thickness of the alloy film layer coated for the thirty-fifth time is controlled to be 42.0 nm, thereby obtaining the thirty-fifth coated glass;
[0251] The thirty-fifth coated glass is subjected to the thirty-sixth coating treatment in the thirty-sixth target chamber, that is, the third coating treatment of the twenty-first silicon-aluminum alloy film is subjected to the magnetron sputtering process conditions of the thirty-sixth coating as shown in Table 1; the metal atoms of the silicon-aluminum alloy target material sintered on the target position of the thirty-sixth target chamber are sputtered from the surface of the target material and deposited on the surface of the thirty-fifth coated glass, and the thickness of the alloy film layer coated for the thirty-sixth time is controlled to be 38.0 nm, thereby obtaining the thirty-sixth coated glass;
[0252] The thirty-sixth coated glass was subjected to the thirty-seventh coating treatment in the thirty-seventh target chamber, that is, the fourth coating treatment of the twenty-first silicon aluminum alloy film was carried out, and the magnetron sputtering process conditions for the thirty-seventh coating are shown in Table 1; the metal atoms of the silicon aluminum alloy target material sintered on the target position of the thirty-seventh target chamber were sputtered from the surface of the target material and deposited on the surface of the thirty-sixth coated glass, and the thickness of the alloy film layer coated for the thirty-seventh time was controlled to be 38.0nm, and the thirty-seventh coated glass was obtained; so far, the coating of the twenty-first silicon aluminum alloy film layer was completed, wherein the thickness of the twenty-first silicon aluminum alloy film layer was 160nm.
[0253] The thirty-seventh coated glass is subjected to the thirty-eighth coating treatment in the target chamber 38, that is, the first coating treatment of the twenty-second zirconium oxide film is carried out. The magnetron sputtering process conditions of the thirty-eighth coating are shown in Table 1. The metal atoms of the zirconium oxide target material sintered on the target position of the target chamber 38 are sputtered from the surface of the target material and deposited on the surface of the thirty-seventh coated glass. The thickness of the alloy film layer of the thirty-eighth coating is controlled to be 12.5 nm, thereby obtaining the thirty-eighth coated glass.
[0254] The thirty-eighth coated glass is subjected to the thirty-ninth coating treatment in the 39th target chamber, that is, the second coating treatment of the twenty-second zirconium oxide film is carried out, and the magnetron sputtering process conditions of the thirty-ninth coating are shown in Table 1; the metal atoms of the zirconium oxide target material sintered on the target position of the 39th target chamber are sputtered from the surface of the target material, and deposited on the surface of the thirty-eighth coated glass, and the thickness of the alloy film layer plated for the thirty-ninth time is controlled to be 12.5nm, and the thirty-ninth coated glass is obtained; at this point, the coating of the twenty-second zirconium oxide film layer is completed, and the thickness of the twenty-second zirconium oxide film layer is 25.0nm.
[0255] Among them, the coating of the first silicon-aluminum alloy film layer forms a base layer firmly bonded to the glass surface on the surface of the original glass sheet, and paves the way for the formation of the glass color; the zinc oxide aluminum alloy film layer plated on the silicon-aluminum alloy film layer plays a bonding role, and the first silicon-aluminum alloy layer and the third nickel-chromium alloy layer are on both sides of the zinc oxide aluminum film layer, and coordinately adjust the visible light transmittance and reduce the technical problem of increased visible light reflectivity caused by the nickel-chromium alloy layer; the nickel-chromium alloy film layer protects the silver layer, improves the bonding degree with the zinc oxide aluminum film layer, and prevents the silver film layer from oxidizing during long-term use, causing the glass color to change with the extension of the use time, and maintains the stability of the glass color; the silver layer is a functional layer, and the first, second, and third silver layers together reduce the plane resistance and emissivity of the entire film layer, and also play a role in adjusting the color and performance of the film layer ( That is, it reduces the shading coefficient, increases the infrared reflectivity, increases the total visible light transmittance, and enhances the thermal insulation performance); the zinc oxide aluminum film layer plays a role in adjusting the transmittance of the film layer; and zinc oxide aluminum has high light transmittance and good conductivity, which can reduce the refractive index of other materials; and has high reflectivity in the infrared band and high absorptivity in the ultraviolet band; the zinc oxide tin film layer is the reflective absorption layer of the coated glass of the present invention, which adjusts the effect of the third layer of silver film layer on the reflection color of the product and reduces the interference of the third layer of silver film on the color of the product; the silicon aluminum alloy film layer is mainly a protective layer and also has a light interference effect; zirconium oxide is the top hard protective layer, which mainly plays the role of a protective film layer during the subsequent deep processing of the product (such as tempering, cutting, edging, cleaning, making hollow glass, etc.); the film layers of the present invention work together to make the product appear light blue.
[0256] The coated glass of the present invention has high infrared reflection, improves the infrared reflectivity of the glass, reduces the heat entering the room through the glass, and has good heat insulation and thermal insulation effects. Moreover, the higher the reflectivity, the less the glass absorbs, and the less glass breakage occurs. The zinc oxide aluminum film layer in the glass of the present invention adjusts the visible light transmittance, and the zinc oxide tin film layer absorbs the reflectivity of the third layer of silver film, and adjusts the front and side colors of the glass.
[0257] In the present invention, the silicon aluminum alloy film layer is plated multiple times; the zinc oxide aluminum alloy film layer is plated multiple times, the zinc oxide tin alloy film layer is plated twice, and the zirconium oxide film layer is plated twice, which not only increases the glass coating thickness, adjusts the color, and protects the film layer; but also improves the production efficiency (speed) in the sputtering process while ensuring the coating thickness, improves the coating uniformity and flatness of the film layer, reduces the scattering of light by the film layer, and avoids color.
[0258] The process parameters of the coating process in Example 1 are shown in Table 1.
[0259] Table 1 Process parameters of coating treatment in Example 1
[0260]
[0261]
[0262] 5. Buffer processing
[0263] The thirty-eighth coated glass is transported from the magnetron sputtering chamber to the pressure buffer chamber, and the pressure in the buffer chamber is gradually increased and the temperature in the buffer chamber is reduced. When the pressure in the buffer chamber finally reaches normal pressure and the temperature in the buffer chamber reaches room temperature, the thirty-eighth coated glass is discharged and stored.
[0264] The low-radiation coated glass of the present invention is a triple-silver Low-E glass with high visible light transmittance, clear glass, light blue color and low shading coefficient. Moreover, the triple-silver glass can also adjust the visible light transmittance according to the thickness of the silver film layer to reduce the shading coefficient, thereby improving the problems of low visible light transmittance and high shading coefficient of double-silver and single-silver coated glass products.
[0265] 6. Tempered treatment
[0266] Place the buffered coated glass on the fully automatic glass cutting machine and cut it into the required size according to the needs. The pressure of the cutting machine is set to ≥6bar, and the cutting wheel angle is selected between 135 and 155°. The cut glass is edged and cleaned (water conductivity ≤20μ / cm / m 2 ) and then sent to a tempering furnace for tempering to obtain tempered coated glass. The tempering furnace heat treatment parameters (taking glass thickness of 6 mm as an example) are shown in Table 1A.
[0267] Table 1A Glass tempering process parameters
[0268]
[0269] The coated glass prepared by the present invention can be tempered (in-situ or off-site tempering). The tempered glass has high visible light transmittance, is clear, and has a light blue color; has a low shading coefficient; and has a relatively high light-to-heat ratio.
[0270] 7. Preparation of conventional insulating glass
[0271] The single piece of low-emissivity coated tempered glass prepared after tempering treatment is made into a hollow glass with a structure of 6 (ie 6mm)-triple silver tempered low-emissivity coated glass (glass) + 12 (ie 12mm)-Air + 6 (ie 6mm)-glass (white glass).
[0272] 8. Preparation of three-glass two-cavity insulating glass
[0273] The single piece of low-emissivity coated tempered glass prepared after tempering treatment is made into a three-glass two-cavity insulating glass with a structure of 6 (i.e. 6mm)-triple silver tempered low-emissivity coated glass (glass) + 12 (i.e. 12mm)-Air + 6 (i.e. 6mm)-glass (white glass) + 12-Air + 6-glass (white glass).
[0274] The present invention is described by taking conventional insulating glass with a structural thickness of 6-triple silver tempered low-emissivity coated glass (glass) + 12-Air + 6-glass (white glass) and a three-glass two-cavity insulating glass of 6-triple silver tempered low-emissivity coated glass (glass) + 12-Air + 6-glass (white glass) + 12-Air + 6-glass (white glass) as examples. Insulating glass with other thicknesses and structures is applicable to the present invention.
[0275] Example 2
[0276] 1. Target sintering
[0277] Same as Example 1.
[0278] 2. Clean the glass
[0279] Except that the temperature of the deionized water used for cleaning is 35°C, the cleaning speed is 3m / min, and the drying temperature is 45°C, the rest is the same as in Example 1;
[0280] 3. Dehumidification and degassing treatment
[0281] The temperature of the first dehumidification and degassing treatment is -135℃ and the absolute pressure is 6.0×10 -2mbar or less; the temperature of the second dehumidification and degassing treatment is 80℃ and the absolute pressure is 6.0×10 -5 Except for being less than mbar, the rest is the same as Example 1.
[0282] 4. Coating treatment
[0283] Except that the process parameters of the coating process are different from those in Example 1, the rest are the same as those in Example 1, wherein the process parameters of the coating process are shown in Table 2.
[0284] Table 2 Process parameters of coating treatment in Example 2
[0285]
[0286]
[0287] 5. Buffer processing
[0288] Same as Example 1.
[0289] 6. Tempered treatment
[0290] Except that the tempering process parameters are as shown in Table 1A, the rest are the same as those in Example 1.
[0291] 7. Preparation of conventional insulating glass
[0292] Same as Example 1.
[0293] 8. Preparation of three-glass two-cavity insulating glass
[0294] Same as Example 1.
[0295] Example 3
[0296] 1. Target sintering
[0297] Same as Example 1.
[0298] 2. Clean the glass
[0299] Except that the temperature of the deionized water for washing is 40°C, the washing speed is 8m / min, and the drying temperature is 55°C, the rest is the same as in Example 1;
[0300] 3. Dehumidification and degassing treatment
[0301] In addition to the first dehumidification and degassing temperature of -145 °C, the second dehumidification and degassing temperature was 100 °C and the absolute pressure was 3.0×10 -5 Except for mbar, the rest is the same as Example 1.
[0302] 4. Coating treatment
[0303] Except that the process parameters of the coating treatment are different from those in Example 1, the rest are the same as those in Example 1, wherein the process parameters of the coating treatment are shown in Table 3.
[0304] Table 3 Process parameters of coating treatment in Example 3
[0305]
[0306]
[0307] 5. Buffer processing
[0308] Same as Example 1.
[0309] 6. Tempered treatment
[0310] Except that the tempering process parameters are as shown in Table 1A, the rest are the same as those in Example 1.
[0311] 7. Preparation of conventional insulating glass
[0312] Same as Example 1.
[0313] 8. Preparation of three-glass two-cavity insulating glass
[0314] Same as Example 1.
[0315] Comparative Example 1
[0316] The pre-treated float glass of Examples 1-3 was tempered, and the tempered glass was used as Control Example 1.
[0317] Comparative Example 2
[0318] The pre-treated float glass sheets in Examples 1-3 were tempered to produce insulating glass with a structure of 6-glass (tempered white glass) + 12Air + 6-glass (white glass) as Control Example 2.
[0319] Comparative Example 3
[0320] Except that the twenty-fourth coated glass is directly sent into the 27th and 28th target chambers for two silicon-aluminum alloy film layer plating treatments, that is, the fourteenth zinc oxide tin film layer plating treatment is not performed, the rest is the same as Example 1.
[0321] Due to the absence of the fourteenth zinc oxide tin film layer, the temperature is unevenly heated during the heat treatment process, causing the three-silver Low-E film layer to be "burned" as a whole by high temperature, "delaminated" over a large area, and the color uniformity of the product to change drastically, resulting in the failure of product development and inability to be applied to actual construction projects.
[0322] Comparative Example 4
[0323] The invention is the same as in Example 1 except that the twenty-fourth coated glass is directly sent into the twenty-ninth target chamber for a zinc oxide aluminum alloy film layer plating treatment, that is, the fourteenth zinc oxide tin film layer and the fifteenth silicon aluminum film layer plating treatment are not performed.
[0324] Because there is no fourteenth zinc oxide tin film layer and fifteenth silicon aluminum film layer, the film layer is easily scratched when the product is processed in the processing steps (cutting, edge grinding, and cleaning processes). During the heat treatment process, due to uneven temperature, the three-silver Low-E film layer will be "burned" as a whole by high temperature, a large area of "film peeling", and the color uniformity of the product will change drastically, resulting in the failure of product development and cannot be applied to actual construction projects.
[0325] Test Example 1: Color, abrasion resistance, and emissivity test
[0326] According to GB / T2680-2021 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet light projection ratio and related window glass parameters of architectural glass" and GB / T 18915.2-2013 "Coated glass Part 2: Low-emissivity coated glass" standards, the color parameters of the single-piece tempered glass and conventional insulating glass prepared in Examples 1-3 and Control Examples 3-4 were measured, and the color parameters of the single-piece glass of Control Example 1 and the insulating glass of Control Example 2 were measured. The measurement results are shown in Tables 4 and 4A.
[0327] Table 4 Test results of performance parameters of conventional insulating glass)
[0328]
[0329] Table 4A Test results of performance parameters of single tempered glass
[0330]
[0331]
[0332] The transmittance color value of the single low-radiation coated triple-silver light blue tempered glass of the present invention is 80≤L * ≤90, -10≤a * ≤-5, -3≤b * ≤3(86≤L * ≤88, -7≤a * ≤-5, 0≤b * ≤1); the glass surface reflection color value is the reflection color value is 28≤L * ≤35,0≤a * ≤5, -15≤b * ≤-8(30≤L * ≤32, 2≤a * ≤4, -11≤b* ≤-9). It is light blue outdoors, colorful, bright and beautiful, and can be widely used in various buildings. The transmittance color value of tempered white glass is: L * 95.8, a * =-1.27, b * is 0.05.
[0333] The light blue tempered glass product film surface prepared in Examples 1-3 has a cool color, which is relatively neutral when seen by people at night or in dark weather, and has a good visual effect. However, the color of Control Example 3 is green, and the color of Control Example 4 is purple-red, and has a poor visual effect.
[0334] The double-glass single-chamber insulating glass prepared by the triple-silver tempered low-emissivity coating prepared by the present invention has the following main visual physical parameters: the transmittance color value is 75≤L * ≤85, -10≤a * ≤-5, -2≤b * ≤3(83≤L * ≤84, -8≤a * ≤-7, 0≤b * ≤1); reflective color value is 30≤L * ≤45, -5≤a * ≤2, -10≤b * ≤-5(39≤L * ≤41, -2≤a * ≤-1, -8≤b * ≤-7), it is light blue outdoors, colorful, bright and beautiful, and can be widely used in various buildings.
[0335] The outdoor reflected color of Example 1 is light blue with a soft color, and the indoor reflected color is a neutral color with a cold tone; the outdoor reflected color of Example 2 is light blue with a soft color, and the indoor reflected color is a neutral color with a slight green and cold tone; while the outdoor reflected color of Example 3 is light blue with a soft color, and the indoor reflected color is a neutral color with a slight red and cold tone; the relative color difference of Examples 1, 2, and 3 is less than 0.5Lab*, the outdoor reflected color is light blue, and the indoor reflected color is a neutral and cold tone; the control example 3 does not have the fourteenth zinc oxide tin film layer, so the outdoor reflected color of the glass is green, and the indoor reflected color is blue-green, which is not a color that people like; the control example 4 does not have the fourteenth zinc oxide tin film layer and the fifteenth silicon aluminum film layer, and the glass not only has a green color outdoors, but also loses the top protective layer during processing, and the yield rate is very low, which basically belongs to the failure of the coating process.
[0336] Test Example 2 Optical Performance Test
[0337] According to GB / T2680-2021 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet projection ratio and related window glass parameters of architectural glass", the optical properties of the insulating glass prepared in Examples 1-3, the single-layer white glass of Control Example 1, and the insulating glass prepared in Control Examples 2-4 were measured, and the test results are shown in Tables 5 and 5A.
[0338] Table 5 Test results of optical properties of conventional insulating glass
[0339]
[0340]
[0341] Table 5A Optical performance test results of triple-glass double-chamber insulating glass
[0342]
[0343] The results of Table 5 and Table 5A show that:
[0344] 1. The conventional insulating glass made of high-quality light blue tempered glass for near-zero energy consumption buildings of the present invention (taking 6 triple silver low-emissivity coated glass (glass) + 12-Ar + 6-glass (white glass) structure as an example) has a visible light transmittance greater than 62%; the visible light outdoor reflectivity is less than 11.5%;
[0345] The three-glass two-chamber insulating glass made of the light blue tempered glass of the present invention (taking the structure of 6 triple silver tempered low-emissivity coated glass (glass) + 12-Ar + 6-glass (white glass) + 12-Ar + 6-glass (white glass) as an example) has a visible light transmittance greater than 56%. The outdoor reflectance of visible light is less than 15%, which is lower than the requirement of less than or equal to 30% specified in GB / T 18091-2015 "Light and Heat Performance of Glass Curtain Walls", indicating that the coated glass of the present invention avoids outdoor "light pollution".
[0346] 2. The conventional insulating glass made of the light blue tempered glass for the near-zero energy consumption building of the present invention (taking the structure of 6 triple silver tempered low-emissivity coated glass (glass) + 12-Ar + 6-glass (white glass) as an example) has a solar transmittance lower than 26%, which is much lower than that of ordinary single-piece white glass and insulating glass made of ordinary glass, indicating that the triple silver low-emissivity coated glass of the present invention effectively controls the entry of sunlight and reduces the large amount of heat contained in sunlight entering the room; and the solar absorption rate is higher than 34.5%;
[0347] The three-glass two-chamber insulating glass made of the low-emissivity coated light blue tempered glass for near-zero energy consumption buildings of the present invention (6 triple-silver tempered low-emissivity coated glass (glass) + 12-Ar + 6-glass (white glass) + 12-Ar + 6-glass (white glass)) has a solar transmittance lower than 23.1%, which is much lower than ordinary single-piece white glass and insulating glass made of ordinary glass, indicating that the triple-silver tempered low-emissivity coated glass of the present invention effectively controls the injection of sunlight and reduces the large amount of heat contained in the sunlight entering the room; and the solar energy absorption rate is higher than 36%, which is significantly higher than ordinary glass and insulating glass made of ordinary glass, indicating that the tempered coated glass of the present invention has a strong ability to maintain indoor and outdoor light and heat environments through its own heat regulation.
[0348] 3. The UV K transmittance, ISO transmittance and transmittance of the insulating glass made of the low-emissivity coated light blue tempered glass of the present invention are significantly lower than those of ordinary glass and the insulating glass made of ordinary glass. Ultraviolet rays have a strong bactericidal and discoloring function. The lower the transmittance, the stronger the ability of the coated glass of the present invention to block ultraviolet rays, thereby avoiding the damage of ultraviolet rays to indoor objects.
[0349] 4. The optical performance technical parameter values of the low-emissivity coated light blue tempered glass of the present invention meet the standards of GB / T18915.2-2013 "Coated Glass Part 2: Low-emissivity Coated Glass", and the maximum allowable deviation of visible light transmittance is small, far lower than the national standard of 2.0%, reaching a maximum allowable deviation of visible light transmittance of less than 0.5%; the color uniformity is high, less than 2.0CIELAB.
[0350] Therefore, the low-radiation coated light blue tempered glass for near-zero energy consumption buildings of the present invention and the hollow glass prepared therefrom are more conducive to creating a bright and comfortable indoor and outdoor light environment, effectively solving the high transmittance and high sunshade characteristics of single-silver low-radiation coated glass, and making the hollow glass with better use effect. It also solves the technical problem that the existing triple-silver coated glass cannot be tempered in a different place, and solves the problem that the existing triple-silver tempered coated glass needs to be tempered first and then coated.
[0351] Test Example 3 Thermal Performance Test
[0352] The thermal properties of the glasses prepared in Examples 1-3 and Comparative Examples 1-4 were measured.
[0353] The measurement is carried out in accordance with the national standard GB / T2680-2021 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet projection ratio and related window glass parameters of architectural glass" and calculated using WINDOW7.8 window curtain wall thermal performance simulation software.
[0354] The test conditions are: winter night: outdoor temperature -18℃, indoor temperature 21℃, wind speed 5.5m / s, no sunlight; summer day: outdoor temperature 32℃, indoor temperature 24℃, wind speed 2.8m / s, solar radiation intensity 783w / ㎡. The test results are shown in Table 6 and Table 6A.
[0355] Table 6 Thermal performance test results of conventional insulating glass
[0356]
[0357] Table 6A Thermal performance test results of triple-glass double-chamber insulating glass
[0358]
[0359] The measurement results in Table 6 show that:
[0360] 1. The heat transfer coefficient K value of the insulating glass prepared by the low-emissivity coated light blue tempered glass for near-zero energy consumption buildings of the present invention is lower than that of ordinary tempered monolithic glass and insulating glass prepared by ordinary tempered glass both in summer daytime and winter night, indicating that the sunlight control coated glass prepared by the present invention can reduce temperature difference heat transfer.
[0361] 2. The three-glass two-cavity insulating glass prepared from the low-emissivity coated light blue tempered glass for near-zero energy consumption buildings of the present invention has a shading coefficient of less than 0.3; the total solar energy transmittance is lower than 26%; the shading coefficient of the prepared conventional insulating glass is less than 0.33; the total solar energy transmittance is lower than 29%. Whether it is three-wave two-cavity or double-glass single-cavity insulating glass, it is significantly lower than ordinary tempered glass and insulating glass made of ordinary tempered glass. The shading coefficient and total solar energy transmittance are important reference factors in building energy-saving calculations. The smaller the value, the better the performance of blocking solar radiation. Therefore, the three-silver tempered low-emissivity coated glass that can be heat-treated off-site and the insulating glass prepared therefrom of the present invention can effectively prevent solar energy from entering the room and being converted into heat energy, thereby reducing refrigeration energy consumption.
[0362] 3. The relative heat gain of the three-glass two-chamber insulating glass made of the low-emissivity coated light blue tempered glass for near-zero energy consumption buildings of the present invention is less than 198W / m 2 , which is significantly lower than the relative heat gain of ordinary tempered glass and insulating glass prepared from ordinary tempered glass. The relative heat gain is the sum of the heat gained and lost through the glass by comprehensively considering the influence of temperature difference heat transfer and solar radiation on the room. The smaller the relative heat gain, the less heat enters the room through the glass, which is more conducive to reducing refrigeration energy consumption. The relative heat gain of the triple-silver tempered low-E coated glass of the present invention is small, indicating that the low-E coated glass that can be heat-treated and processed off-site prepared by the present invention has good energy-saving effect.
[0363] In conclusion, the low-emissivity coated tempered glass for near-zero energy consumption buildings of the present invention can more effectively prevent heat energy from entering the room than ordinary glass and its insulating glass, and can reduce refrigeration energy consumption while achieving the purpose of energy saving and environmental protection. The effect is even better when made into insulating glass.
[0364] In summary, the low-emissivity coated tempered glass for near-zero energy consumption buildings of the present invention is not only beautiful in appearance, bright in color and decorative in effect, but also conducive to forming a comfortable and pleasant light and heat environment, and has a relatively ideal effect when made into three-glass two-chamber insulating glass, compared with the test example.
Claims
1. A light blue tempered glass, comprising a composite metal film layer laminated on a tempered glass substrate, characterized in that: The composite metal film layer includes three layers of metal silver film layers, wherein the transmittance color value of the low-emissivity coated tempered glass is 80≤L * ≤90, -10≤a * ≤-5, -3≤b * ≤3; reflective color value is 28≤L * ≤35,0≤a * ≤5, -15≤b * ≤-8.
2. The low-emissivity coated tempered glass according to claim 1, characterized in that: The first metal silver film layer is close to the tempered glass substrate, and between the first metal silver film layer and the tempered glass substrate are the silicon aluminum film layer, the zinc oxide aluminum film layer, and the nickel chromium film layer in sequence; the third metal silver film layer is far away from the tempered glass substrate, and between the third metal silver film layer and the glass surface are the nickel chromium film layer, the zinc oxide aluminum film layer, the silicon aluminum film layer, and the zirconium oxide film layer in sequence; the second metal silver film layer is arranged between the first and third metal silver film layers.
3. The low-emissivity coated tempered glass according to claim 1 or 2, characterized in that: The thickness of the first metal silver film layer is 8.0-15.0 nm; the thickness of the second metal silver film layer is 5.0-15.0 nm; and the thickness of the third metal silver film layer is 8.0-15.0 nm.
4. The low-emissivity coated tempered glass according to claim 1 or 2, characterized in that: The thickness of the first metal silver film layer is 10.0-13.0 nm; the thickness of the second metal silver film layer is 8.0-10.0 nm; and the thickness of the third metal silver film layer is 10.0-13.0 nm.
5. A light blue tempered glass comprising a tempered glass substrate (1) and a composite metal film layer laminated on the tempered glass substrate, characterized in that: The composite metal film layer comprises: A first silicon-aluminum alloy film layer (2) is located on the surface of the tempered glass substrate; a second zinc-oxide aluminum alloy film layer (3) is located on the surface of the first silicon-aluminum alloy film layer; a third nickel-chromium alloy film layer (4) is located on the surface of the second zinc-oxide aluminum alloy film layer; a fourth silver film layer (5) is located on the surface of the third nickel-chromium alloy film layer; a fifth nickel-chromium alloy film layer (6) is located on the surface of the fourth silver film layer; a sixth zinc-oxide aluminum alloy film layer (7) is located on the surface of the fifth nickel-chromium alloy film layer; a seventh silicon-aluminum alloy film layer (8) is located on the surface of the sixth zinc-oxide aluminum alloy film layer; an eighth zinc-oxide aluminum alloy film layer (9) is located on the surface of the seventh silicon-aluminum alloy film layer; a ninth nickel-chromium alloy film layer (10) is located on the surface of the eighth zinc-oxide aluminum alloy film layer; a tenth silver film layer (11) is located on the surface of the ninth nickel-chromium alloy film layer; an eleventh nickel-chromium alloy film layer (12) is located on the surface of the tenth silver film layer; a twelfth zinc-oxide aluminum alloy film layer (13) is located on the surface of the eleventh The surface of the nickel-chromium alloy film layer; the thirteenth silicon-aluminum alloy film layer (14), which is located on the surface of the twelfth zinc-oxide aluminum alloy film layer; the fourteenth zinc-tin oxide alloy film layer (15), which is located on the surface of the thirteenth silicon-aluminum alloy film layer; the fifteenth silicon-aluminum alloy film layer (16), which is located on the surface of the fourteenth zinc-tin oxide alloy film layer; the sixteenth zinc-oxide aluminum alloy film layer (17), which is located on the surface of the fifteenth silicon-aluminum alloy film layer; the seventeenth nickel-chromium alloy film layer (18), which is located on the surface of the sixteenth zinc-oxide aluminum alloy film layer; the eighteenth silver film layer (19), which is located on the surface of the seventeenth nickel-chromium alloy film layer; the nineteenth nickel-chromium alloy film layer (20), which is located on the surface of the eighteenth silver film layer; the twentieth zinc-oxide aluminum alloy film layer (21), which is located on the surface of the nineteenth nickel-chromium alloy film layer; the twenty-first silicon-aluminum alloy film layer (22), which is located on the surface of the twentieth zinc-oxide aluminum alloy film layer; the twenty-second zirconium oxide film layer (23), which is located on the surface of the twenty-first silicon-aluminum alloy film layer.
6. The light blue tempered glass as claimed in claim 5, characterized in that: The thickness of the first silicon-aluminum alloy film layer is 55.0-65.0 nm; the thickness of the second zinc-oxide aluminum alloy film layer is 10.0-30.0 nm; the thickness of the third nickel-chromium alloy layer is 0.5-3.0 nm; the thickness of the fourth silver film layer is 8.0-15.0 nm; the thickness of the fifth nickel-chromium alloy film layer is 0.5-3.0 nm; the thickness of the sixth zinc-oxide aluminum alloy film layer is 15.0-25.0 nm; the thickness of the seventh silicon-aluminum alloy film layer is 300.0-420.0 nm; the thickness of the eighth zinc-oxide aluminum alloy film layer is 15.0-25.0 nm; the thickness of the ninth nickel-chromium alloy film layer is 1.0-5.0 nm; the thickness of the tenth silver film layer is 5.0-15.0 nm; the thickness of the eleventh nickel-chromium alloy film layer is 1.5-3.5 nm; the thickness of the twelfth zinc-oxide aluminum alloy film layer is The thickness is 15.0-50.0nm; the thickness of the thirteenth silicon aluminum alloy film layer is 130.0-200.0nm; the thickness of the fourteenth zinc oxide tin alloy film layer is 15.0-40.0nm; the thickness of the fifteenth silicon aluminum alloy film layer is 110.0-150.0nm; the thickness of the sixteenth zinc oxide aluminum alloy film layer is 15.0-30.0nm; the thickness of the seventeenth nickel chromium alloy film layer is 1.0-3.0nm; the thickness of the eighteenth silver film layer is 8.0-15.0nm; the thickness of the nineteenth nickel chromium alloy film layer is 1.0-3.0nm; the thickness of the twentieth zinc oxide aluminum alloy film layer is 10.0-30.0nm; the thickness of the twenty-first silicon aluminum alloy film layer is 150.0-180.0nm; the thickness of the twenty-second zirconium oxide alloy film layer is 10.0-50.0nm.
7. The light blue tempered glass as claimed in claim 5, characterized in that: The thickness of the first silicon aluminum alloy film layer is 55.3-61.7nm; the thickness of the second zinc oxide aluminum alloy film layer is 15.0-25.0nm; the thickness of the third nickel chromium alloy layer is 1.0-2.0nm; the thickness of the fourth silver film layer is 10.0-13.0nm; the thickness of the fifth nickel chromium alloy film layer is 1.0-2.0nm; the thickness of the sixth zinc oxide aluminum alloy film layer is 18.0-23nm; the thickness of the seventh silicon aluminum alloy film layer is 320.0-350.0nm; the thickness of the eighth zinc oxide aluminum alloy film layer is 15-22.0nm; the thickness of the ninth nickel chromium alloy film layer is 2.0-4.0nm; the thickness of the tenth silver film layer is 8.0-10.0nm; the thickness of the eleventh nickel chromium alloy film layer is 1.5-2.5nm; the thickness of the twelfth zinc oxide aluminum alloy film layer is The thickness of the thirteenth silicon aluminum alloy film layer is 140.0-170.0nm; the thickness of the fourteenth zinc oxide tin alloy film layer is 20.0-35.0nm; the thickness of the fifteenth silicon aluminum alloy film layer is 114-128.0nm; the thickness of the sixteenth zinc oxide aluminum alloy film layer is 17.0-25.0nm; the thickness of the seventeenth nickel chromium alloy film layer is 1.5-2.5nm; the thickness of the eighteenth silver film layer is 10.0-13.0nm; the thickness of the nineteenth nickel chromium alloy film layer is 1.5-2.5nm; the thickness of the twentieth zinc oxide aluminum alloy film layer is 15.0-25.0nm; the thickness of the twenty-first silicon aluminum alloy film layer is 155.0-170.0nm; the thickness of the twenty-second zirconium oxide alloy film layer is 20.0-35.0nm.
8. The light blue tempered glass according to any one of claims 5 to 7, characterized in that One surface of the glass substrate is stacked with, from bottom to top, the first silicon-aluminum alloy film layer, the second zinc-oxide-aluminum alloy film layer, the third nickel-chromium alloy film layer, the fourth silver film layer, the fifth nickel-chromium alloy film layer, the sixth zinc-oxide-aluminum alloy film layer, the seventh silicon-aluminum alloy film layer, the eighth zinc-oxide-aluminum alloy film layer, the ninth nickel-chromium alloy film layer, the tenth silver film layer, the eleventh nickel-chromium-gold film layer, the twelfth zinc-oxide-aluminum alloy film layer, the thirteenth silicon-aluminum alloy film layer, the fourteenth zinc-tin oxide-alloy film layer, the fifteenth silicon-aluminum alloy film layer, the sixteenth zinc-oxide-aluminum alloy film layer, the seventeenth nickel-chromium alloy film layer, the eighteenth silver film layer, the nineteenth nickel-chromium alloy film layer, the twentieth zinc-oxide-aluminum alloy film layer, the twenty-first silicon-aluminum alloy film layer, and the twenty-second zirconium oxide film layer.
9. The light blue tempered glass according to any one of claims 5 to 7, characterized in that: The transmittance color value of the single low-emissivity coated tempered glass is 80≤L * ≤90, -10≤a * ≤-5, -3≤b * ≤3; reflective color value is 28≤L * ≤35,0≤a * ≤5, -15≤b * ≤-8.
10. A light blue tempered glass, characterized in that: Prepared according to the following steps in the following order: 1) Sintering target The target materials silicon aluminum alloy, zinc oxide aluminum alloy, nickel chromium alloy, silver, zinc oxide tin, and zirconium oxide are sintered on the target position of the vacuum sputtering chamber of the glass coating machine respectively for standby use; 2) Glass pretreatment The glass substrate to be coated is placed in a vacuum state to perform dehumidification and degassing treatment to reduce the moisture and gas deposited on the glass surface to obtain a dehumidified and degassed glass substrate; 3) Coating treatment The dehumidified and degassed glass substrate is sent into the vacuum magnetron sputtering chamber of the glass coating machine which is sintered with silicon aluminum alloy, zinc oxide aluminum alloy, nickel chromium alloy, silver, zinc oxide tin alloy and zirconium oxide target respectively, and the first silicon aluminum film layer; the second zinc oxide aluminum film layer; the third nickel chromium alloy film layer; the fourth silver film layer; the fifth nickel chromium alloy film layer; the sixth zinc oxide aluminum film layer; the seventh silicon aluminum film layer; the eighth zinc oxide aluminum film layer; the ninth nickel chromium alloy film layer; the tenth silver film layer; the eleventh nickel chromium gold film layer; the twelfth zinc oxide aluminum film layer; the thirteenth silicon aluminum film layer; the fourteenth zinc oxide tin film layer; the fifteenth silicon aluminum film layer; plating treatment of the sixteenth zinc oxide aluminum film layer; the seventeenth nickel-chromium alloy film layer; the eighteenth silver film layer; the nineteenth nickel-chromium alloy film layer; the twentieth zinc oxide aluminum film layer; the twenty-first silicon aluminum film layer; and the twenty-second zirconium oxide film layer; 4) Tempered treatment The coated glass is sent into a tempering furnace for tempering to produce low-emissivity coated tempered glass.
Citation Information
Cited By
Preparation method of low-radiation coated tempered glass
CN119661089A
Preparation method of low-emissivity coated tempered glass
CN119661089B
Method for preparing low-radiation coated tempered glass
CN119683865A
Method for preparing low-emissivity coated tempered glass
CN119683865B
Preparation method of tempered low-emissivity coated glass
CN119683867A